Strengthened microcrystalline glass with high drop resistance and preparation method and application

By optimizing the glass formula and heat treatment conditions, the problems of poor deep stress characteristics and unsatisfactory drop resistance in the existing spinel microcrystalline glass are solved, and efficient and economical reinforced microcrystalline glass preparation is achieved, with excellent drop impact resistance and reduced preparation costs.

CN118184152BActive Publication Date: 2025-04-01CHONGQING AUREAVIA HI TECH GLASS CO LTD

Patent Information

Application Number
CN202211739751.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-30
Publication Date
2025-04-01
Estimated Expiration
2042-12-30

AI Technical Summary

Technical Problem

After chemical strengthening, the existing spinel microcrystalline glass has poor deep stress characteristics and poor drop resistance. It requires high-temperature heat treatment during preparation, which limits its mass production.

Method used

By optimizing the glass formula, the use of Li2O is reduced, the content of Na2O and Al2O3 is increased, the dosage relationship of each oxide is adjusted, the heat treatment temperature is reduced, and the reinforced microcrystalline glass with excellent surface stress characteristics and deep stress characteristics are formed.

Benefits of technology

It has achieved excellent anti-fall impact performance of reinforced microcrystalline glass, reduced preparation costs, simplified mass production processes, and met the industry's energy-saving and carbon reduction needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118184152B_ABST
    Figure CN118184152B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of microcrystalline glass, and in particular to a strengthened microcrystalline glass with high drop resistance, a preparation method and an application thereof, wherein the strengthened microcrystalline glass comprises a compressive stress layer and a tensile stress layer, and a spinel crystal is the main crystalline phase; the composition of the strengthened microcrystalline glass substantially does not contain Li 2 O; the strengthened glass-ceramics meets the following requirements: CS_50≥100MPa, |CT_AV|≥70MPa, DOL_0≥0.13t, where t is the thickness of the glass-ceramics. The strengthened glass-ceramics of the present invention have excellent deep stress characteristics, which, combined with the high intrinsic strength originally possessed by the glass-ceramics, give the strengthened glass-ceramics excellent mechanical properties, especially drop impact resistance. The strengthened glass-ceramics of the present invention can achieve a drop impact resistance effect that is far superior to that of existing spinel glass-ceramics, and can meet the application requirements of cover glass for high-end electronic products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of microcrystalline glass, and in particular to a reinforced microcrystalline glass with high drop resistance, a preparation method and an application thereof. Background Art

[0002] As electronic devices become thinner and lighter, the performance requirements for cover glass are gradually increasing. For electronic cover glass, it is necessary to have excellent surface stress characteristics and excellent deep stress characteristics to obtain high mechanical properties. Among them, excellent deep stress characteristics are a necessary condition for cover glass to obtain excellent impact resistance, such as excellent drop resistance.

[0003] Glass-ceramic (glass ceramic) materials have become a better choice for screen covers due to their excellent mechanical properties and light transmittance. Among the many glass-ceramics, spinel glass-ceramics with spinel as the main crystal phase has gradually attracted the attention of industry insiders due to its high Young's modulus and shear modulus.

[0004] In order to make spinel glass-ceramics meet the requirements of screen cover, researchers tried to chemically strengthen and toughen it. The main method is to first introduce lithium oxide and / or sodium oxide into the substrate glass, and then achieve chemical strengthening by exchanging lithium ions in the substrate glass with sodium ions in the salt bath, and / or exchanging sodium ions in the substrate glass with potassium ions in the salt bath.

[0005] After research, the inventors found that there are many disadvantages in using lithium ions to achieve chemical strengthening and toughening. First, the radius difference between Li ions and Na ions is about 22pm, and the radius difference between Na ions and K ions is about 40pm. The stress performance is caused by the "crowding" effect formed by ion exchange. Therefore, under the same exchange amount, the stress performance generated by the exchange of Li ions and Na ions is far inferior to the stress performance generated by the exchange of Na ions and K ions. Second, if you want to rely on the exchange of Li ions and Na ions to obtain high stress performance, you need to add a higher content of lithium oxide to the substrate glass. Li 2 O is expensive, and the use of large amounts of lithium oxide will result in excessively high costs for glass. Thirdly, if there is a large amount of Li in the substrate glass, it is easy to cause the substrate glass to precipitate quartz, quartz solid solution and other impurities that affect the transmittance of the microcrystalline glass when it is heat-treated to obtain microcrystalline glass, resulting in poor optical properties of the microcrystalline glass.

[0006] As for the solution of using sodium ions to achieve chemical strengthening and toughening in the prior art, the inventors found that its deep stress characteristics are poor and the effect of anti-drop impact is not ideal. For example, the invention application CN111908793A discloses a glass ceramic with a spinel crystal phase, the components of which are SiO 2:50~70mol%Al 2 O 3 :5~21mol%Na 2 O: 6~21mol%, ZnO: 2~12mol%, TiO 2 :0.5~10mol%MgO:0~10mol%; a large amount of Na 2 However, after chemical strengthening, the glass ceramic can only obtain a compressive stress layer depth of no more than 40 microns, and the deep stress characteristics are poor. After falling and impacting, it is very easy to break, and it is difficult to achieve an excellent anti-falling and impacting effect.

[0007] In addition, the inventors also found that the heat treatment temperature required for the preparation of existing transparent spinel glass-ceramics, mainly the crystallization temperature, is usually 900°C or even higher, which greatly limits the mass production of spinel glass-ceramics and makes it impossible to successfully mass-produce ordinary roller kilns. Summary of the invention

[0008] Based on the above research, in order to improve economic benefits and avoid the drawbacks of using lithium ions to achieve chemical strengthening and toughening in spinel glass-ceramics, the inventors came up with the idea of ​​using sodium ions instead of lithium oxide to achieve chemical strengthening and toughening of spinel glass-ceramics.

[0009] However, the transparent spinel glass-ceramics in the prior art that is chemically strengthened and toughened only by sodium ions has poor anti-drop performance and cannot meet the drop impact performance requirements of the screen cover; and the existing transparent spinel glass-ceramics has a crystallization temperature higher than 900°C, which affects the mass production performance.

[0010] After in-depth research, the inventors found that the reason why the existing spinel glass-ceramics containing only Na cannot reach a higher stress depth after chemical strengthening, has poor deep stress characteristics, and poor drop resistance is mainly because the microstructure of the existing spinel glass-ceramics limits the depth of Na ions entering the interior of the glass, affecting the depth at which Na ions and K ions can exchange. [AlO 4 ]The volume of the tetrahedron is larger than that of [SiO 4 ], theoretically, if Al 2 O 3 The content of Al should be able to broaden the ion exchange channel and promote the diffusion of Na ions. 2 O 3 After that, the melting difficulty of the substrate glass will be greatly increased, especially in the absence of Li 2 O flux. Because Na 2 O is not as effective as Li in fluxing 2O, while Al 2 O 3 The melting difficulty is higher than that of SiO 2 By introducing a large amount of Na 2 O will not play a fluxing effect, which will lead to uncontrollable crystallization and ceramicization of the substrate glass during the molding or annealing process.

[0011] In this regard, the inventors continuously adjusted the formula, adjusted the amount of each oxide in the formula and the relationship between the amounts of each oxide, optimized the glass formula, took into account the melting effect, optical effect and mechanical properties, and finally developed a lithium-free transparent spinel glass-ceramic with a specific structure, good overall uniformity and high intrinsic strength, that is, chemically strengthened glass-ceramic. The chemically strengthened glass-ceramic not only has a lower preparation cost than the existing lithium-containing spinel glass-ceramic, excellent optical properties, and high intrinsic strength, but also can be obtained by chemical strengthening. Strengthened glass-ceramic with excellent surface stress characteristics and deep stress characteristics, thereby enabling the strengthened glass-ceramic to obtain excellent mechanical properties, such as excellent drop impact resistance. At the same time, the substrate glass corresponding to the optimized glass formula of the present invention can obtain a chemically strengthened glass-ceramic with a main crystal phase of zinc-magnesium spinel solid solution, excellent optical properties and high intrinsic strength when the heat treatment temperature does not exceed 800°C. Compared with the prior art, the optimized chemically strengthened glass-ceramics formula of the present invention can significantly reduce the heat treatment temperature required to prepare the target glass-ceramics, meet the industry's development needs of energy conservation and carbon reduction, improve the mass producibility of transparent spinel glass-ceramics, and ensure the excellent optical properties and high intrinsic strength of chemically strengthened glass-ceramics.

[0012] Specifically, the present invention provides the following technical solutions:

[0013] In one aspect, the present invention provides a strengthened glass-ceramic, wherein the strengthened glass-ceramic comprises a compressive stress layer and a tensile stress layer, the strengthened glass-ceramic comprises spinel crystals, and the spinel crystals are the main crystalline phase of the strengthened glass-ceramic;

[0014] The composition of the strengthened glass-ceramics substantially does not contain Li 2 O, in mol%, Li 2 O is less than 0.01%;

[0015] The strengthened microcrystalline glass satisfies: CS_50≥100MPa, |CT_AV|≥70MPa, DOL_0≥0.13t, t is the thickness of the microcrystalline glass in μm, the unit of DOL_0 is μm, and the units of CS_50 and |CT_AV| are MPa.

[0016] Preferably, the above-mentioned strengthened microcrystalline glass satisfies 500MPa≥CS_50≥140MPa; and / or 200MPa≥|CT_AV|≥70MPa; and / or 0.22t≥DOL_0≥0.15t.

[0017] Preferably, the tempered glass-ceramics has |CT_CV|≥80MPa, preferably 300MPa≥|CT_CV|≥80MPa, where the unit of |CT_CV| is MPa.

[0018] Preferably, the surface K of the strengthened microcrystalline glass 2 The O concentration is ≥ 9.00 wt %, preferably 9.00 to 16.00 wt %.

[0019] Preferably, the CT_LD of the strengthened glass-ceramics is 40000 MPa / mm-85000 MPa / mm, preferably 45000 MPa / mm-85000 MPa / mm, and more preferably 48000 MPa / mm-85000 MPa / mm.

[0020] Preferably, the crystallinity of the strengthened microcrystalline glass is ≥20.00wt%; preferably, the crystallinity is 20.00-50.00wt%; further preferably, the crystallinity is 30.00-50.00wt%; more preferably, the crystallinity is 35.00-45.00wt%.

[0021] Preferably, in the strengthened glass-ceramics, the average grain size is ≤15.0 nm, preferably 1.0 to 15.0 nm, more preferably 1 to 10 nm, and more preferably 4.5 to 8.0 nm; and / or, the spinel crystal is (Zn, Mg)Al 2 O 4 ; and / or, the strengthened microcrystalline glass also includes secondary crystalline phase tetragonal zirconia.

[0022] Preferably, the strengthened glass-ceramics is transparent in the visible light range.

[0023] Preferably, the Vickers hardness of the strengthened glass-ceramics is 700-900 kgf / mm 2 .

[0024] Preferably, the fracture toughness of the strengthened microcrystalline glass is greater than or equal to 1.00 MPa·m 1 / 2 , preferably greater than or equal to 1.20 MPa·m 1 / 2 , more preferably greater than or equal to 1.50 MPa·m 1 / 2 .

[0025] Preferably, at a thickness of 0.7 mm, the tempered glass-ceramics is subjected to a sandpaper drop resistance test using 120-mesh sandpaper, and the average sandpaper drop resistance height of the tempered glass-ceramics is greater than 1.5 m, preferably greater than or equal to 1.80 m, further preferably 1.80 to 2.50 m, and more preferably 2.00 to 2.50 m; the average sandpaper drop resistance height is based on tests of at least 10 samples.

[0026] Preferably, at a thickness of 0.7 mm, the tempered glass-ceramics is subjected to a 2.5 m drop test using 120-mesh sandpaper. If the glass sample does not break after falling, it is marked as passed. The pass rate of the tempered glass-ceramics is ≥50%, preferably ≥60%, and more preferably ≥70%. The pass rate is based on the testing of at least 10 samples.

[0027] Preferably, the composition of the strengthened microcrystalline glass tensile stress layer comprises, in terms of mol% of oxides: SiO 2 38.00~48.00%,Al 2 O 3 25.50~30.00%, ZrO 2 3.00~5.00%, MgO 5.00~8.00%, ZnO8.00~14.00%, Na 2 O 7.20~14.00%, B 2 O 3 3.00~8.00%, K 2 O 0~2.00% and Y 2 O 3 0~1.00%.

[0028] Preferably, in the tensile stress layer of the strengthened glass-ceramics:

[0029] The glass composition of the tensile stress layer of the strengthened glass-ceramics satisfies the following conditions, expressed in terms of the content expressed as a molar percentage of oxides:

[0030] The value of A is calculated based on the following formula (1), and the value of A is less than or equal to 0.18, and the preferred value of A is 0.05 to 0.15.

[0031] (1) A = 0.65 × Al 2 O 3 +3.5×ZrO 2 -0.8×Na 2 O-2.5×B 2 O 3 ;

[0032] and / or,

[0033] The value of B is calculated based on the following formula (2), and the value of B is less than or equal to 0.80, and the preferred value of B is 0.60 to 0.78.

[0034] (2) B = 3.8 × Na 2 O+B 2 O 3 +4.5×MgO+6.0×ZnO-0.4×Al 2 O 3 -SiO 2 .

[0035] Preferably, in the tensile stress layer of the strengthened glass-ceramics, the SiO 2 The molar percentage is 38.00-44.00%;

[0036] And / or, the Na 2 The molar percentage of O is 7.20 to 13.00%, preferably 7.20 to 12.00%;

[0037] And / or, the Al 2 O 3 The molar percentage is 25.50-28.00%;

[0038] And / or, the molar percentage of MgO is 5.00-7.00%, preferably 5.00-6.50%;

[0039] And / or, the molar percentage of ZnO is 8.00-12.00%, preferably 8.00-10.50%;

[0040] and / or, said B 2 O 3 The molar percentage is 3.00 to 7.00%, preferably 3.00 to 6.50%.

[0041] Preferably, in the tensile stress layer of the strengthened glass-ceramics, Al 2 O 3 The molar percentages of the components of Al, MgO, and ZnO satisfy the following relationship: 2 O 3 -MgO-ZnO=8.00~15.00%.

[0042] Preferably, in the tensile stress layer of the strengthened glass-ceramics:

[0043] The glass composition of the tensile stress layer of the strengthened glass-ceramics satisfies the following conditions, expressed in terms of the content expressed as a molar percentage of oxides:

[0044] The value of X is calculated based on the following formula (3), and the value of X is 30.00 to 50.00%, preferably 34.00 to 46.00%.

[0045] (3)X=2.1×(Al 2 O 3 -MgO-ZnO) / (SiO 2 +Al 2 O 3 -MgO-ZnO+Na 2 O+K 2 O+B 2 O 3 );

[0046] and / or,

[0047] The value of Y is calculated based on the following formula (4), and the value of Y is 60.00 to 80.00%, preferably 60.00 to 75.00%.

[0048] (4)Y=(2.7×Na 2 O+1.8×(Al 2 O 3 -MgO-ZnO)) / (SiO 2 +Al 2 O 3 -MgO-ZnO+Na 2 O

[0049] +K 2 O+B 2 O 3 ).

[0050] Preferably, the tensile stress layer of the strengthened glass-ceramics: substantially does not contain BaO, with BaO less than 0.01% in mol%; and / or substantially does not contain TiO 2 , in mol%, TiO 2 Less than 0.01%.

[0051] Preferably, the Young's modulus of the strengthened glass-ceramics is ≥ 100 GPa, preferably Young's modulus ≥

[0052] 110 GPa, more preferably 114 GPa ≤ Young's modulus ≤ 140 GPa.

[0053] On the other hand, the present invention also provides a method for preparing the above-mentioned strengthened glass-ceramics, comprising the following steps: (I) preparation of chemically strengthened glass-ceramics: the chemically strengthened glass-ceramics are prepared from substrate glass by heat treatment, (II) preparation of strengthened glass-ceramics: chemically strengthening the chemically strengthened glass-ceramics obtained in step (I) to obtain the above-mentioned strengthened glass-ceramics;

[0054] The strengthened glass-ceramics includes spinel crystals, and the spinel crystals are the main crystal phase of the strengthened glass-ceramics;

[0055] The composition of the strengthened glass-ceramics substantially does not contain Li 2 O, in mol%, Li 2 O is less than 0.01%;

[0056] The strengthened microcrystalline glass satisfies: CS_50≥100MPa, |CT_AV|≥70MPa, DOL_0≥0.13t, where t is the thickness of the microcrystalline glass.

[0057] Preferably, in the above preparation method, the chemical strengthening treatment includes a single-step strengthening method or a multi-step strengthening method; preferably, the salt bath for the chemical strengthening treatment is a molten salt containing a potassium salt.

[0058] Preferably, in the above preparation method, the concentration of potassium salt in the salt bath for chemical strengthening treatment is 60wt% to 100wt%; preferably, the temperature of the salt bath for chemical strengthening treatment is 380°C to 600°C, preferably 400°C to 550°C.

[0059] On the other hand, the present invention also provides a chemically strengthened glass-ceramic for preparing the above-mentioned strengthened glass-ceramic, wherein the chemically strengthened glass-ceramic contains spinel crystals, and the spinel crystals are the main crystal phase of the chemically strengthened glass-ceramic;

[0060] The chemically strengthened glass-ceramics contains the following oxides in mol%: SiO 2 38.00~48.00%,Al 2 O 3 25.50~30.00%, ZrO 2 3.00~5.00%, MgO 5.00~8.00%, ZnO 8.00~14.00%, Na 2 O 7.20~14.00%, B 2 O 3 3.00~8.00%, K 2 O 0~2.00% and Y 2 O 3 0~1.00%;

[0061] Wherein, the chemically strengthened glass-ceramics contains substantially no Li 2 O, in mol%, Li 2 O is less than 0.01%.

[0062] Preferably, the composition of the chemically strengthened glass-ceramics, expressed in terms of the content expressed in molar percentage of oxides, satisfies:

[0063] A=0.65×Al 2 O3 +3.5×ZrO 2 -0.8×Na 2 O-2.5×B 2 O 3 , wherein A≤0.18, preferably the value of A is 0.05 to 0.15;

[0064] and / or, B = 3.8 × Na 2 O+B 2 O 3 +4.5×MgO+6.0×ZnO-0.4×Al 2 O 3 -SiO 2 , wherein B≤0.80, preferably the value of B is 0.60 to 0.78;

[0065] and / or, X = 2.1 × (Al 2 O 3 -MgO-ZnO) / (SiO 2 +Al 2 O 3 -MgO-ZnO+Na 2 O+K 2 O+B 2 O 3 ), wherein X=30.00-50.00%, preferably X=34.00-46.00%;

[0066] And / or, Y = (2.7 × Na 2 O+1.8×(Al 2 O 3 -MgO-ZnO)) / (SiO 2 +Al 2 O 3 -MgO-ZnO+Na 2 O+K 2 O+B 2 O 3 ), wherein Y=60.00-80.00%, preferably Y=60.00-75.00%;

[0067] And / or, in the chemically strengthened glass-ceramics, Al 2 O 3 The molar percentages of the components of Al, MgO, and ZnO satisfy the following relationship: 2 O 3 -MgO-ZnO=8.00~15.00%.

[0068] Preferably, in the above-mentioned chemically strengthened glass-ceramics, the spinel crystal is (Zn, Mg)Al 2 O4 ; and / or, the chemically strengthened glass-ceramics further comprises secondary crystalline tetragonal zirconia;

[0069] And / or, the crystallinity of the chemically strengthened glass-ceramics is ≥20.00wt%; preferably, the crystallinity is 20.00-50.00wt%; further preferably, the crystallinity is 30.00-50.00wt%; more preferably, the crystallinity is 35.00-45.00wt%;

[0070] And / or, in the chemically strengthened glass-ceramics, the average grain size is ≤15.0 nm, preferably 1.0 to 15.0 nm, more preferably 1.0 to 10.0 nm, and more preferably 4.5 to 8.0 nm;

[0071] And / or, the Young's modulus of the chemically strengthened glass-ceramics is ≥100 GPa, preferably ≥110 GPa, and more preferably 114 GPa≤Young's modulus≤140 GPa.

[0072] On the other hand, the present invention also provides the use of the above-mentioned strengthened microcrystalline glass or the strengthened microcrystalline glass prepared by the above-mentioned preparation method or the above-mentioned chemically strengthened microcrystalline glass in mobile phone displays, tablet computer displays, handheld game consoles, electronic terminals, portable digital devices, vehicle central control screens, electronic whiteboard glass, smart home touch screens, vehicle windshields, aircraft windshields or aircraft windshields.

[0073] Beneficial effects of the present invention:

[0074] The present invention has conducted an in-depth study on the intrinsic strength of chemically strengthened glass-ceramics and the stress characteristics that can be obtained by the glass after strengthening. By strengthening a specific system of chemically strengthened glass-ceramics with high intrinsic strength to meet specific stress characteristics, a strengthened glass-ceramics with excellent mechanical properties, especially excellent drop impact resistance, is finally obtained. In the present invention, the strengthened glass-ceramics meets: CS_50≥100MPa, |CT_CV|≥80MPa, |CT_AV|≥70MPa, DOL_0≥0.13t, and has excellent deep stress characteristics. Combined with the high intrinsic strength that the glass-ceramics originally possesses, the strengthened glass-ceramics are endowed with excellent mechanical properties, especially drop impact resistance. The strengthened glass-ceramics of the present invention can achieve a drop impact resistance effect that is far superior to the existing spinel glass-ceramics, and can meet the application requirements of cover glass for high-end electronic products.

[0075] In addition, since the present invention optimizes the formula of chemically strengthened glass-ceramics, it not only improves the economic benefits, but also reduces the difficulty of mass production of glass-ceramics and improves the mass production performance. Specifically, the chemically strengthened glass-ceramics of the present invention does not need to use expensive lithium, and can also obtain excellent surface stress characteristics and deep stress characteristics through chemical strengthening, thereby obtaining excellent drop impact resistance. Compared with the existing lithium aluminum silicon glass-ceramics, the strengthened glass-ceramics of the present invention have a comparable drop impact resistance effect, but the cost has been greatly reduced, and it has great market value. At the same time, the substrate glass corresponding to the optimized glass formula of the present invention has low melting difficulty, is not prone to melting defects, and can obtain chemically strengthened glass-ceramics with a main crystal phase of zinc-magnesium spinel solid solution and excellent optical properties and high intrinsic strength when the heat treatment temperature does not exceed 800°C, which greatly reduces the difficulty of mass production of chemically strengthened glass-ceramics, and the possibility of mass production is higher, which meets the development needs of the industry for energy conservation and carbon reduction. BRIEF DESCRIPTION OF THE DRAWINGS

[0076] Figure 1 This is a diagram of the melting results of the substrate glass of Example 1;

[0077] Figure 2 This is a diagram showing the melting results of the substrate glass of Example 3;

[0078] Figure 3 This is a diagram showing the melting results of the substrate glass of Example 4;

[0079] Figure 4 This is an appearance diagram of the chemically strengthened glass-ceramics of Example 4;

[0080] Figure 5 This is an appearance diagram of the chemically strengthened glass-ceramics of Example 5;

[0081] Figure 6 is a thermogravimetric analysis curve of the substrate glass of Example 1;

[0082] Figure 7 is the XRD diffraction pattern of the chemically strengthened glass-ceramics of Example 1;

[0083] Figure 8 1 is the transmittance curve of the chemically strengthened glass-ceramics of Example 5 under different wavelength conditions;

[0084] Fig. 9 This is a diagram of the melting results of the substrate glass of Comparative Example 1;

[0085] Fig.10 This is a diagram showing the melting results of the substrate glass of Comparative Example 2;

[0086] Fig.11 This is a diagram of the melting results of the substrate glass of Comparative Example 3;

[0087] Fig.12 This is a diagram of the melting results of the substrate glass of Comparative Example 6;

[0088] Fig.13 This is the appearance of the chemically strengthened microcrystalline glass of Comparative Example 19. DETAILED DESCRIPTION

[0089] In the present invention, unless otherwise specified in specific circumstances, the numerical ranges listed herein include upper and lower limits, and "above" and "below" include the endpoint values, as well as all integers and fractions within the range, and are not limited to the specific values ​​listed when the range is defined. "And / or" referred to herein is inclusive, for example, "A; and / or B" means only A, or only B, or both A and B.

[0090] As used herein, the language "substantially free of" or "free of" when used to describe constituent components of a composition, batch, melt or article refers to constituent components that have not been actively added or dosed into the composition, batch, melt or article but may be present in small amounts of less than about 0.01% (on an oxide mole basis) as a contaminant and / or due to the inherent degree of uncertainty attributable to any measurement or analytical technique.

[0091] In the present invention, the chemically strengthened glass-ceramics is a type of solid composite material that is prepared by targeted controlled heat treatment of the substrate glass and contains both a glass phase and a crystal phase (microcrystalline phase, crystalline phase, crystalline phase). It should be understood that both the crystal phase and the crystal grain refer to the crystals precipitated in the glass-ceramics, but the description methods are different. The crystal phase is the microscopic structure of the crystal, which is determined by the conformation and arrangement of the polymer chains in the crystal.

[0092] In the present invention, strengthened glass-ceramics refers to a solid composite material obtained by chemically strengthening glass-ceramics, also known as chemically strengthened glass-ceramics.

[0093] It should be understood that during high-temperature chemical strengthening treatment, the alkali metal ions with large ionic radius (such as potassium ions and sodium ions) in the salt bath / molten salt will replace the alkali metal ions with small ionic radius (such as sodium ions and lithium ions) in the microcrystalline glass, thereby generating an exchange ion volume difference and generating compressive stress on the surface of the microcrystalline glass.

[0094] In the present invention, the base glass refers to glass that has not been subjected to nucleation treatment, crystallization treatment, and strengthening treatment.

[0095] In the present invention, nucleation treatment refers to growing small crystal nuclei from nucleating substances in the glass through heat treatment; crystallization treatment refers to growing certain crystals based on the crystal nuclei through heat treatment.

[0096] In the present invention, the nucleation temperature refers to the temperature at which crystal nuclei are formed.

[0097] In the present invention, the crystallization temperature refers to the temperature at which the target crystal growth rate can be controlled.

[0098] In the present invention, the optical b value represents the yellow-blue value of the material. The optical b value in the present invention is the b value of transmitted light. A positive optical b value indicates that the material is blue.

[0099] Transmittance refers to the ratio of the radiation energy projected and transmitted through the object to the total radiation energy projected on the object during the process of the incident light flux leaving from the illuminated surface or the incident surface of the medium to the other side. It should be understood that when a certain wavelength is irradiated on the glass surface, light will be reflected, absorbed and transmitted, and the ratio of the intensity of the transmitted part to the intensity of the incident light is the transmittance.

[0100] In the present invention, the transmittance result of the microcrystalline glass at a wavelength of 550nm refers to the average transmittance of multiple glass samples of the same batch measured at a wavelength of 550nm, and at least 5 samples of each batch of microcrystalline glass are taken for testing. In the present invention, a Konica Minolta spectrophotometer CM-3600A is used to test the transmittance of each glass sample at a wavelength of 550nm.

[0101] In the present invention, fogging refers to a semi-transparent state due to larger crystals or phase separation in the microcrystalline glass / glass ceramics, which is a state between transparency and devitrification.

[0102] In the present invention, devitrification means that due to the large crystals or phase separation in the microcrystalline glass / glass ceramic, the transparent property of the glass is completely lost, and any image on the back cannot be seen through the glass.

[0103] In the present invention, SOC refers to the photoelastic coefficient. Photoelasticity mainly refers to the phenomenon of birefringence caused by anisotropy of transparent materials after being subjected to force. The value of the residual stress (MPa) inside the material can be obtained by measuring the photoelastic coefficient and birefringence.

[0104] In the present invention, the surface K 2 O concentration is equal to K 2 O mass / total oxide mass, where the total oxide mass includes SiO 2 、Al 2 O 3 , P 2 O 5 、ZrO 2 、Na 2 O.K 2 O and other oxides can be accurately tested by XRF, excluding Li 2 O.B 2 O 3XRF cannot accurately test the content of the oxides obtained. XRF testing uses a standardless test and does not test the concentration of elements with atomic numbers 6 and below or their oxides in the glass. That is, the K obtained by XRF testing in the present invention is 2 When calculating the O concentration, the total mass of oxides does not include the mass of elements with atomic numbers 6 and below or their oxides in the glass.

[0105] In the present invention, Vickers hardness refers to a standard for expressing the hardness of a material proposed by Robert L. Smith and George E. Sandland of the United Kingdom at Vickers Ltd in 1921.

[0106] In the present invention, fracture toughness refers to the impedance value displayed by the material when there is a crack or a crack-like defect in the sample or component and the material no longer breaks rapidly with the increase of load, that is, when the so-called unstable fracture occurs.

[0107] In the present invention, CS_50 refers to the compressive stress value at a depth of 50 μm from the glass surface.

[0108] In the present invention, |CT_CV| refers to the absolute value of the maximum value of the tensile stress, specifically refers to the absolute value of the maximum value of all tensile stresses in the tensile stress layer.

[0109] In the present invention, |CT_AV| refers to the absolute value of the average tensile stress in the tensile stress layer, specifically refers to the absolute value of the average value of all tensile stresses in the tensile stress layer.

[0110] In the present invention, DOL_0 refers to the depth of the compressive stress layer, also known as the depth of the compressive stress layer, which refers to the distance from any surface of the glass to a position close to the surface where the compressive stress is zero.

[0111] In a first aspect, the present invention provides a strengthened glass-ceramic having the following crystallization characteristics and stress characteristics in order to make the strengthened glass-ceramic have excellent drop resistance.

[0112] In a specific embodiment of the present invention, a strengthened microcrystalline glass with high drop resistance comprises a compressive stress layer and a tensile stress layer, wherein the strengthened microcrystalline glass comprises spinel crystals, and the spinel crystals are the main crystalline phase of the strengthened microcrystalline glass; the composition of the strengthened microcrystalline glass substantially does not contain Li 2 O; the strengthened microcrystalline glass satisfies: CS_50≥100MPa, |CT_AV|≥70MPa, DOL_0≥0.13t, t is the thickness of the strengthened microcrystalline glass.

[0113] The general drop impact is a piercing type of damage. Sharp particles can easily break through the glass surface CS under impact, causing a pit with a depth of 30-50 microns. Then, cracks are formed at the pit and extend, breaking through the compressive stress area, thus breaking the glass. CS_50 represents the magnitude of the compressive stress at a depth of 50 microns. The greater the stress at this point, the more conducive it is to inhibit the formation of cracks at the pit. The deeper the DOL-0, the larger the area that hinders crack extension. CT-CV is the highest point of tensile stress, which is similar to the average value of tensile stress of CT-AV. It indirectly indicates the magnitude of deep compressive stress. The better the stress performance, the more difficult it is for cracks to extend.

[0114] The present invention has conducted an in-depth study on the intrinsic strength of glass-ceramics and the stress characteristics that can be obtained by strengthening the glass-ceramics after strengthening. By strengthening a specific system of glass-ceramics with high intrinsic strength to meet specific stress characteristics, a strengthened glass-ceramics with excellent mechanical properties, such as excellent drop impact resistance, is finally obtained. In the present invention, by giving the strengthened glass-ceramics excellent surface stress characteristics and deep stress characteristics, combined with the high intrinsic strength that the glass-ceramics originally possessed, the mechanical properties of the strengthened glass-ceramics are ultimately greatly improved, so that the strengthened glass-ceramics can achieve a drop impact resistance effect that is far superior to the existing spinel glass-ceramics.

[0115] The inventors of the present invention have found that the tempered microcrystalline glass with specific stress characteristics can improve the tolerance of the tempered microcrystalline glass to damage and destruction caused by collision with sharp-angle objects such as sand, thereby obtaining excellent impact and drop resistance.

[0116] In some preferred embodiments of the present invention, CS_50 is 140 MPa to 500 MPa, |CT_AV| is above 70 MPa, preferably 70 to 200 MPa and DOL_0 ≥ 0.13 t, preferably 0.15 t to 0.22 t, where t is the thickness of the strengthened glass-ceramics.

[0117] In some specific embodiments of the present invention, the thickness t of the strengthened glass-ceramics is 0.2-5.0 mm, preferably 0.3-2.0 mm, and more preferably 0.4-1.5 mm.

[0118] In some preferred embodiments of the present invention, the strengthened glass-ceramics satisfies: CS_50≥100MPa, preferably 500MPa≥CS_50≥140MPa. In some embodiments, CS_50 may be 140-480MPa, 140-460MPa, 140-440MPa, 140-420MPa, 140-400MPa, 140-380MPa, 140-360MPa, 140-340MPa, 160-480MPa, 180-480MPa, 200-480MPa, 220-480MPa, 240-480MPa, 260-480MPa or 280-480MPa. In some embodiments, the CS_50 of the strengthened glass-ceramics may be 100 MPa, 140 MPa, 160 MPa, 180 MPa, 200 MPa, 220 MPa, 240 MPa, 260 MPa, 280 MPa, 300 MPa, 320 MPa, 340 MPa, 360 MPa, 380 MPa, 400 MPa, 420 MPa, 440 MPa, 460 MPa, 480 MPa or 500 MPa, or a CS_50 within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the glass having the desired performance of the present invention can be obtained.

[0119] In some preferred embodiments of the present invention, the strengthened glass-ceramics satisfies: |CT_AV|≥

[0120] 70MPa, preferably 200MPa≥|CT_AV|≥70MPa. In some embodiments, |CT_AV| may be 70-180MPa, 70-160MPa, 70-140MPa, 70-120MPa, 70-100MPa, 90-180MPa, 110-180MPa, 130-180MPa or 150-180MPa. In some embodiments, |CT_AV| of the above-mentioned strengthened microcrystalline glass may be 70MPa, 90MPa, 110MPa, 120MPa, 140MPa, 160MPa, 180MPa or 200MPa, or a |CT_AV| in a numerical range consisting of any two of the above-mentioned specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the glass with the desired properties of the present invention can be obtained.

[0121] In some preferred embodiments of the present invention, the strengthened glass-ceramics satisfies: the depth of the compressive stress layer DOL_0 ≥ 0.13t, preferably 0.22t ≥ DOL_0 ≥ 0.15t, where t is the thickness of the glass-ceramics. In some embodiments, DOL_0 may be 0.15t to 0.21t, 0.15t to 0.20t, 0.15t to 0.19t, 0.15t to 0.18t, 0.15t to 0.17t, 0.16t to 0.21t, 0.17t to 0.21t, 0.18t to 0.21t or 0.19t to 0.21t. In some embodiments, the DOL_0 of the strengthened glass-ceramics may be 0.13t, 0.15t, 0.16t, 0.17t, 0.18t, 0.19t, 0.20t, 0.21t or 0.22t, or within the numerical range DOL_0 formed by any two of the above specific values ​​as endpoints. Exemplarily, when the thickness of the strengthened glass-ceramics is 0.7 mm, the depth of the compressive stress layer DOL_0 is ≥ 91.00 μm, preferably 105-150 μm, and the depth of the compressive stress layer DOL_0 may be 91.00 μm, 105.00 μm, 112.00 μm, 119 μm, 126.00 μm, 133.00 μm, 140.00 μm, 147.00 μm or 154.00 μm, or within the numerical range DOL_0 formed by any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the glass with the desired properties of the present invention can be obtained.

[0122] In some preferred embodiments of the present invention, |CT_CV|≥80MPa, preferably 80~

[0123] 300MPa.

[0124] In some preferred embodiments of the present invention, the strengthened glass-ceramics satisfies: |CT_CV|≥

[0125] 80MPa, preferably 300MPa≥|CT_CV|≥80MPa. In some embodiments, |CT_CV| can be 80-280MPa, 80-260MPa, 80-240MPa, 80-220MPa, 80-200MPa, 80-180MPa, 80-160MPa, 100-280MPa, 120-280MPa, 140-280MPa, 160-280MPa or 180-280MPa. In some embodiments, the |CT_CV| of the strengthened glass-ceramics may be 80 MPa, 100 MPa, 120 MPa, 140 MPa, 160 MPa, 180 MPa, 200 MPa, 220 MPa, 240 MPa, 260 MPa, 280 MPa or 300 MPa, or within a numerical range of |CT_CV| consisting of any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the glass having the desired properties of the present invention can be obtained.

[0126] In the present invention, CT_LD refers to tensile stress linear density, which is the ratio of the absolute value of the sum of tensile stresses of the strengthened microcrystalline glass measured by the SLP-2000 stress meter to the glass thickness. The microcrystalline glass is placed in a salt bath for ion exchange to form a compressive stress layer (i.e., a strengthening layer). During the ion exchange process, a tensile stress layer is formed inside the glass. The tensile stress layer has an upper boundary at a certain distance from the upper surface of the strengthened microcrystalline glass and a lower boundary at a certain distance from the lower surface of the strengthened glass. The tensile stress at a certain point on the line segment in the tensile stress layer, which is perpendicular to the upper boundary and the lower boundary and whose upper and lower endpoints fall on the upper boundary and the lower boundary respectively, is recorded as the tensile stress curve. The ratio of the definite integral of the tensile stress curve to the thickness of the strengthened microcrystalline glass is recorded as the tensile stress linear density. The tensile stress linear density of the strengthened microcrystalline glass of the present invention can reach 40000MPa / mm-85000MPa / mm.

[0127] In some preferred embodiments of the present invention, the strengthened glass-ceramics satisfies: CT_LD is 40000MPa / mm-85000MPa / mm, preferably 45000MPa / mm-85000MPa / mm, and more preferably 48000MPa / mm-85000MPa / mm. In some embodiments, CT_LD can be 40000-80000MPa / mm, 40000-75000MPa / mm, 40000-70000MPa / mm, 40000-

[0128] 65000MPa / mm, 40000~60000MPa / mm, 45000-85000MPa / mm,

[0129] 50000MPa / mm-85000MPa / mm, 55000MPa / mm-85000MPa / mm,

[0130] In some embodiments, the tensile stress line density CT_LD of the strengthened glass-ceramics may be 40000MPa / mm, 45000MPa / mm, 50000MPa / mm, 55000MPa / mm, 60000MPa / mm, 65000MPa / mm,

[0131] 70000MPa / mm, 75000MPa / mm, 80000MPa / mm or 85000MPa / mm, or a tensile stress linear density CT_LD within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired properties of the present invention can be obtained.

[0132] In some preferred embodiments of the present invention, the surface K of the strengthened microcrystalline glass 2 O concentration ≥

[0133] 9.00 wt%, preferably 9.00 to 16.00 wt%. In some embodiments, the surface K 2 The O concentration may be 9.00-15.00 wt%, 9.00-14.00 wt%, 9.00-13.00 wt%, 9.00-12.00 wt%, 9.00-11.00 wt%, 10.00-16.00 wt%, 11.00-16.00 wt%, 12.00-16.00 wt%, 13.00-16.00 wt% or 14.00-16.00 wt%. In some embodiments, the surface K of the strengthened microcrystalline glass 2 The O concentration may be 9.00 wt%, 10.00 wt%, 11.00 wt%, 12.00 wt%, 13.00 wt%, 14.00 wt%, 15.00 wt% or 16.00 wt%, or a surface K value within a numerical range consisting of any two of the above specific values ​​as endpoints. 2 O concentration. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired properties of the present invention can be obtained.

[0134] In some preferred embodiments of the present invention, in the strengthened glass-ceramics, the spinel crystal is (Zn, Mg)Al 2 O 4 In some preferred embodiments of the present invention, the strengthened glass-ceramics further comprises secondary crystalline tetragonal zirconia.

[0135] In some preferred embodiments of the present invention, the strengthened glass-ceramics is transparent in the visible light range.

[0136] In some preferred embodiments of the present invention, the Vickers hardness of the strengthened glass-ceramics is 700-900 kgf / mm 2 In some embodiments, the Vickers hardness may be 700 to 890 kgf / mm 2 ,700~880kgf / mm 2 、700~870kgf / mm 2 ,700~860kgf / mm 2 ,700~850kgf / mm 2 、700~840kgf / mm 2 ,700~830kgf / mm 2 ,700~820kgf / mm 2 、700~810kgf / mm 2 ,700~800kgf / mm 2 、710~900kgf / mm 2 ,720~900kgf / mm 2 ,730~900kgf / mm 2 ,740~900kgf / mm 2 ,750~900kgf / mm 2 ,760~900kgf / mm 2 ,770~900kgf / mm 2 ,780~900kgf / mm 2 ,790~900kgf / mm 2 or 800~900kgf / mm 2 In some embodiments, the Vickers hardness of the strengthened glass-ceramics may be 700 kgf / mm 2 、710kgf / mm 2 、720kgf / mm 2 、730kgf / mm 2 、740kgf / mm 2 、750kgf / mm 2 , 760kgf / mm2, 770kgf / mm2 、780kgf / mm 2 、790kgf / mm 2 、800kgf / mm 2 、810kgf / mm 2 、820kgf / mm2、830kgf / mm 2 、840kgf / mm 2 、850kgf / mm 2 、860kgf / mm 2 、870kgf / mm 2 、880kgf / mm 2 、890kgf / mm 2 or 900kgf / mm 2 , or a Vickers hardness within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired properties of the present invention can be obtained.

[0137] In some preferred embodiments of the present invention, the fracture toughness of the strengthened glass-ceramics is greater than or equal to 1.00 MPa·m 1 / 2 , preferably greater than or equal to 1.20 MPa·m 1 / 2 , more preferably greater than or equal to 1.50 MPa·m 1 / 2 In some embodiments, the fracture toughness may be 1.00 to 2.00 MPa·m 1 / 2 , 1.20~2.00MPa·m 1 / 2 1.40~2.00MPa·m 1 / 2 , 1.50~2.00MPa·m 1 / 2 1.00~1.80MPa·m 1 / 2 1.00~1.60MPa·m 1 / 2 , 1.00~1.40MPa·m 1 / 2 or 1.00~1.20MPa·m 1 / 2 In some embodiments, the fracture toughness may be 1.00 MPa·m 1 / 2 , 1.20MPa·m 1 / 2 , 1.30MPa·m 1 / 2 , 1.40MPa·m 1 / 2 , 1.50MPa·m 1 / 2 , 1.51MPa·m 1 / 2 , 1.57MPa·m 1 / 2 , 1.60MPa·m 1 / 2 , 1.64MPa·m 1 / 2, 1.66MPa·m 1 / 2 , 1.70MPa·m 1 / 2 、1.80MPa·m 1 / 2 , 1.90MPa·m 1 / 2 or 2.00MPa·m 1 / 2 , or the fracture toughness within the numerical range formed by any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired properties of the present invention can be obtained.

[0138] In some preferred embodiments of the present invention, at a thickness of 0.7 mm, the tempered glass-ceramics is subjected to a sandpaper drop resistance test using 120-grit sandpaper, and the average sandpaper drop resistance height of the tempered glass-ceramics is greater than 1.5 m, preferably greater than or equal to 1.80 m, more preferably 1.80 to 2.50 m, and more preferably 2.00 to 2.50 m; the average sandpaper drop resistance height is based on the test of at least 10 samples. In some embodiments, the average sandpaper drop resistance height may be 1.80 m, 2.00 m, 2.10 m, 2.20 m, 2.30 m, 2.40 m, or 2.50 m, or the average sandpaper drop resistance height is within the numerical range formed by any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the glass with the desired performance of the present invention can be obtained.

[0139] In some preferred embodiments of the present invention, at a thickness of 0.7 mm, the tempered glass-ceramics is subjected to a 2.5 m drop test using 120-mesh sandpaper. If the glass sample does not break after falling, it is recorded as passed, and the pass rate of the tempered glass-ceramics is ≥50%, preferably ≥60%, more preferably ≥70%, and more preferably, the pass rate is 60% to 100%; the pass rate is based on the test of at least 10 samples. In some embodiments, the pass rate of the tempered glass-ceramics in the 2.5 m drop test (120-mesh sandpaper) can be 60%, 70%, 80%, 90% or 100%, or the pass rate of the 2.5 m drop test (120-mesh sandpaper) within the numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass with the desired performance of the present invention can be obtained.

[0140] In a second aspect, the present invention provides a chemically strengthened glass-ceramic, which is prepared from a substrate glass by heat treatment; the chemically strengthened glass-ceramic can obtain the above-mentioned strengthened glass-ceramic after chemical strengthening treatment; the chemically strengthened glass-ceramic contains spinel crystals, and the spinel crystals are the main crystalline phase of the glass-ceramic.

[0141] In the present invention, the composition of the chemically strengthened glass-ceramics can be obtained by semi-quantitative analysis using a fluorescent X-ray method, or can be measured by a wet analysis method such as ICP emission analysis.

[0142] It should be noted that, unless otherwise specified, the content of each component is expressed as a molar percentage based on the oxide.

[0143] After in-depth research, the inventors found that the reason why the existing spinel glass-ceramics containing only Na cannot reach a higher stress depth after chemical strengthening, has poor deep stress characteristics, and poor drop resistance is mainly because the microstructure of the existing spinel glass-ceramics limits the depth of Na ions entering the interior of the glass, affecting the depth at which Na ions and K ions can exchange. [AlO 4 ]The volume of the tetrahedron is larger than that of [SiO 4 ], theoretically, if Al 2 O 3 The content of Al should be able to broaden the ion exchange channel and promote the diffusion of Na ions. 2 O 3 After that, the melting difficulty of the substrate glass will be greatly increased, especially in the absence of Li 2 O flux. Because Na 2 O is not as effective as Li in fluxing 2 O, while Al 2 O 3 The melting difficulty is higher than that of SiO 2 By introducing a large amount of Na 2 O will not play a fluxing effect, which will lead to uncontrollable crystallization and ceramicization of the substrate glass during the molding or annealing process.

[0144] In order to achieve a strengthened glass-ceramic that satisfies the above-mentioned crystallization characteristics and stress characteristics, and to obtain a strengthened glass-ceramic with excellent anti-drop performance, the inventors have continuously adjusted the formula, adjusted the amount of each oxide in the formula and the amount relationship of each oxide, and taken into account the melting effect, optical effect, stress effect and anti-drop effect, and provided a chemically strengthened glass-ceramic with the following composition, which contains the following oxides in mol%: SiO 2 38.00~48.00%,Al 2 O 325.50~30.00%, ZrO 2 3.00~5.00%, MgO 5.00~8.00%, ZnO 8.00~14.00%, Na 2 O 7.20~14.00%, B 2 O 3 3.00~8.00%, K 2 O 0~2.00% and Y 2 O 3 0~1.00%; wherein the chemically strengthened glass-ceramics substantially does not contain Li 2 O, in mol%, Li 2 O is less than 0.01%.

[0145] It should be understood that the composition of the substrate glass is the same as the composition of the chemically strengthened glass-ceramics of the present invention, measured in mol% of oxides. After the chemical strengthening ion exchange process, the composition at the surface of the chemically strengthened glass-ceramics or substrate glass may be different from the composition of the newly formed chemically strengthened glass-ceramics or substrate glass (i.e., chemically strengthened glass-ceramics or substrate glass that has not undergone ion exchange). That is, the composition of the compressive stress layer formed on the surface of the strengthened glass-ceramics by ion exchange may be different from the composition of the chemically strengthened glass-ceramics. This is because during ion exchange, one type of alkali metal ion (for example, Li + Or Na + ) are replaced by larger alkali metal ions (e.g., Na + or K + ) is replaced by, such as Na in glass + K in strengthening salt bath + Exchange, K + Replaced by, and / or, Li in glass + and Na in the strengthening salt bath + Exchange, by Na + However, in the embodiment, the composition of the chemically strengthened glass-ceramics or substrate glass at the center of the depth of the glass product or near the center of the depth still has the composition of the newly formed glass-ceramics or substrate glass. That is, in the present invention, the composition of the tensile stress layer of the strengthened glass-ceramics still has the composition of the chemically strengthened glass-ceramics described above.

[0146] Next, the range of each component (ingredient) of the chemically strengthened glass-ceramics of the present invention will be described.

[0147] The inventors have found that in the formula system of the present invention, Na 2The proper increase of O content helps the chemical strengthening of glass-ceramics to obtain higher stress characteristics, including high surface stress characteristics and high deep stress characteristics, and can also reduce the melting temperature and the temperature of crystal precipitation. 2 Too low an O content is not only not conducive to strengthening the microcrystalline glass to obtain high stress characteristics, but also leads to an increase in the heat treatment temperature, increasing the difficulty of mass production of microcrystalline glass. In addition, during the heat treatment process, it is easy to cause direct phase separation or precipitation of impurities that affect the optical properties of the microcrystalline glass, resulting in translucent or even opaque microcrystalline glass. 2 Excessive addition of O will affect the network structure of the glass due to the provision of a large amount of free oxygen, and it is also easy to cause the substrate glass to be ceramicized during the annealing process or the precipitation of impurities that affect the optical properties of the microcrystalline glass during the heat treatment of the substrate glass to prepare the microcrystalline glass, thereby reducing the transmittance of the obtained microcrystalline glass. Therefore, in the present invention, Na is expressed in mol%. 2 The O content is 7.20 to 14.00%, preferably 7.20 to 13.00%, and more preferably 7.20 to 12.00%.

[0148] In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass of the present invention may contain 7.20-13.50%, 7.20-13.00%, 7.20-12.50%, 7.20-12.00%, 7.20-11.50%, 7.20-11.00%, 7.20-10.50%, 7 .20-10.00%, 7.20-9.50%, 7.20-9.00%, 7.70-14.00%, 8.20-14.00%, 8.70-14.00%, 9.20-14.00%, 9.20-14.00%, 10.20-14.00%, 10.70-14.00%, or 11.50-14.00% Na 2 In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass of the present invention may contain Na in a molar percentage of 7.20%, 7.70%, 8.20%, 8.70%, 9.20%, 9.70%, 10.20%, 10.70%, 11.20%, 11.50%, 12.20%, 12.70%, 13.20%, 13.70% or 14.00%, or in a numerical range consisting of any two of the above specific values ​​as endpoints. 2 O. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass with the desired properties of the present invention can be obtained.

[0149] The inventors found that SiO 2It is the oxide that forms the glass network and is an indispensable component of the glass network structure. 2 The content of SiO can increase the stability and mechanical strength of the glass, but excessive SiO 2 It will increase the viscosity of the substrate glass, making it more difficult to melt the glass, thereby reducing the formability of the substrate glass. 2 The content is 38.00-48.00%, preferably 38.00-44.00%.

[0150] In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass of the present invention may contain 38.00% to 48.00%, 38.50% to 48.00%, 39.00% to 48.00%, 40.00% to 48.00%, 42.00% to 48.00%, 44.00% to 48.00%, 38.00% to 46.00%, 38.00% to 44.00%, 38.00% to 42.00% or 38.00% to 40.00% of SiO 2 In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass of the present invention may contain 38.00%, 38.50%, 39.00%, 40.00%, 41.00%, 42.00%, 43.00%, 44.00%, 45.00%, 46.00%, 47.00% or 48.00% SiO 2 , or SiO within the numerical range formed by any two of the above specific values ​​as endpoints 2 It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass with the desired properties of the present invention can be obtained.

[0151] The inventors have found that in the formulation system of the present invention, Al 2 O 3 The appropriate addition of Al can not only promote the precipitation of the main crystal phase spinel, inhibit the precipitation of other impurities such as quartz ss that affect the optical properties of the microcrystalline glass of this system, but also increase the ion exchange rate during the strengthening process and promote the ion exchange. 2 O 3 This will lead to a sharp increase in the difficulty of melting the substrate glass, and at the same time accelerate the crystallization rate of the substrate glass, making it easy for the substrate glass to crystallize and lose clarity during the normal cooling process during preparation. Therefore, in the present invention, Al is expressed in mol%. 2 O 3 The content is 25.50 to 30.00%, preferably 25.50 to 28.00%.

[0152] In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass of the present invention may contain 25.50-29.50%, 25.50-29.00%, 25.50-28.50%, 25.50-28.00%, 25.50-27.50%, 25.50-27.00%, 25.50-26.50%, 26.00-30.00%, 26.50-30.00%, 27.00-30.00%, 27.50-30.00%, 28.00-30.00%, 28.50-30.00% or 29.00-30.00% Al 2 O 3 In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass of the present invention may contain 25.50%, 26.00%, 26.50%, 27.00%, 27.50%, 28.00%, 28.50%, 29.00%, 29.50% or 30.00% Al 2 O 3 , or Al within the numerical range formed by any two of the above specific values ​​as endpoints 2 O 3 It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass with the desired properties of the present invention can be obtained.

[0153] The inventors have found that in the formula system of the present invention, MgO and ZnO, as the main components of spinel, can promote the precipitation of spinel when added in appropriate amounts, and can also reduce the difficulty of melting the substrate glass to a certain extent. However, the addition of excessive MgO and ZnO often causes the spinel grains to grow very easily, and it is difficult to obtain microcrystalline glass with high transparency. That is, the content relationship of MgO and ZnO largely determines whether the microcrystalline glass sample can be transparent and whether the optical properties are excellent. Therefore, in the present invention, in terms of mol%, the MgO content is 5.00% to 8.00%, preferably 5.00 to 7.00%, and more preferably 5.00 to 6.50%; the ZnO content is 8.00% to 14.00%, preferably 8.00 to 12.00%, and more preferably 8.00 to 10.50%.

[0154] In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or substrate glass of the present invention may contain MgO with a molar percentage of 5.50% to 8.00%, 6.00% to 8.00%, 6.50% to 8.00%, 7.00 to 8.00%, 5.00% to 7.50%, 5.00% to 7.00%, 5.00% to 6.50% or 5.00% to 6.00%. In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or substrate glass may contain MgO with a molar percentage of 5.00%, 5.50%, 6.00%, 6.50%, 7.00%, 7.50 or 8.00%, or MgO within a numerical range consisting of any two of the above specific numerical values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the glass with the desired properties of the present invention can be obtained.

[0155] In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass of the present invention may contain a molar percentage of 8.50% to 14.00%, 9.00% to 14.00%, 9.50% to 14.00%, 10.00 to 14.00%, 10.50 to 14.00%, 11.00 to 14.00%, 11.50 to 14.00%, 12.00 to 14.00%, 8.00 to 13.50, 8.00 to 13.00, 8.00 to 12.50, 8.00 to 12.00, 8.00 to 11.50, 8.00 to 11.00, 8.00 to 10.50 or 8.00 to 10.00% ZnO. In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass of the present invention may contain 8.00%, 8.50%, 9.00%, 9.50%, 10.00%, 10.50%, 11.00%, 11.50%, 12.00%, 12.50%, 13.00%, 13.50% or 14.00% ZnO in molar percentage, or ZnO in a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired performance of the present invention can be obtained.

[0156] The inventors have found that in the formulation system of the present invention, ZrO 2 As an effective nucleating agent, ZrO 2 First precipitated from the glass in the form of crystals, ZrO 2 The crystal becomes the nucleus for the subsequent growth of the main crystal spinel. Within a certain glass composition range, ZrO 2The content of ZrO will affect the formation of the substrate glass, the crystal shape, crystal type and crystal size of the microcrystalline glass after the substrate glass is heat treated. Therefore, in the present invention, in terms of mol%, ZrO 2 The content is 3.00 to 5.00%, preferably 3.00 to 4.00%.

[0157] In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass of the present invention may contain 3.50-5.00%, 4.00-5.00%, 4.50-5.00%, 3.00-4.50%, 3.00-4.00% or 3.00-3.50% ZrO 2 In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass of the present invention may contain 3.00%, 3.50%, 4.00%, 4.50% or 5.00% ZrO 2 , or ZrO within the numerical range formed by any two of the above specific values ​​as endpoints 2 It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass with the desired properties of the present invention can be obtained.

[0158] The inventors have found that in the formula system of the present invention, an appropriate amount of B 2 O 3 It can not only greatly reduce the difficulty of melting the substrate glass, but also help promote the precipitation of the main crystal phase spinel. 2 O 3 If the amount added is too low, it is easy to cause melting defects in the preparation of the substrate glass. 2 O 3 The addition of B may easily lead to opacity of the glass when the substrate glass is heat treated to prepare the microcrystalline glass. At the same time, it may lead to the precipitation of other impurity crystal phases, which seriously affects the transparency of the microcrystalline glass. Therefore, in the present invention, B is calculated in mol%. 2 O 3 The content of is 3.00 to 8.00%, preferably 3.00 to 7.00%, and more preferably 3.00 to 6.50%.

[0159] In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass of the present invention may contain 3.50-8.00%, 4.00-8.00%, 4.50-8.00%, 5.00-8.00%, 5.50-8.00%, 6.00-8.00%, 6.50-8.00%, 7.00-8.00%, 3.00-7.50%, 3.00-7.00%, 3.00-6.50%, 3.00-6.00%, 3.00-5.50%, 3.00-5.00%, 3.00-4.50% or 3.00-4.00% B 2 O 3 In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass may contain 3.00%, 3.50%, 4.00%, 4.50%, 5.00%, 5.50%, 6.00%, 6.50%, 7.00%, 7.50% or 8.00% B 2 O 3 , or B within the numerical range formed by any two of the above specific values ​​as endpoints 2 O 3 It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass with the desired properties of the present invention can be obtained.

[0160] In order to ensure the melting effect and optical properties of the glass, Na 2 O+B 2 O 3 10.20 to 20.00%, preferably 10.20 to 18.00%. 2 O+B 2 O 3 The coordination with the overall composition can solve the melting problem and make the substrate glass obtain better optical properties. 2 O and B 2 O 3 The increase in Al 2 O 3 Melting problems caused by increased content.

[0161] The inventors have found that in the formula system of the present invention, although BaO can improve the melting effect of the base glass and inhibit the growth of grains to a certain extent, thereby improving the optical properties of the microcrystalline glass, it has a strong inhibitory effect on the Na-K exchange, which is not conducive to the chemical strengthening of the microcrystalline glass. Therefore, it is preferably not added in the present invention, and the BaO content is less than 0.01% in mol%.

[0162] The inventors have found that in the formulation system of the present invention, TiO 2 When added as a nucleating agent, it will cause the substrate glass to have an undesirable color. In order to obtain the desired transparent colorless microcrystalline glass, the present invention preferably does not contain TiO 2 , in mol%, TiO 2 Less than 0.01%.

[0163] The inventors have found that in the formulation system of the present invention, K 2 O is an optional component that helps improve the low temperature melting property and formability of glass. + Radius larger than Na + , add appropriate amount of K 2 O can reduce the tendency of glass to crystallize and increase the transparency and gloss of glass. 2 O, not only is it easy to reduce the chemical stability and hardness of the glass, but it is also easy to make the glass crystallize stronger, the glass is easy to lose clarity, and the crystallized glass is easy to break. Therefore, in the present invention, K is expressed in mol%. 2 The content of O is 0 to 2.00%.

[0164] The inventors have found that in the formulation system of the present invention, Y 2 O 3 It is an optional component that improves the hardness and chemical stability of glass ceramics and inhibits the crystallization of glass. 2 O 3 It can improve the density of the glass phase, thereby improving the overall strength of the microcrystalline glass. At the same time, it can be combined with ZrO 2 Forming a eutectic, reducing ZrO when melting in a furnace 2 The unevenness caused by precipitation. 2 O 3 When the content is too high, it will affect the precipitation of spinel crystals and reduce the chemical strengthening performance of glass and glass ceramics. 2 O 3 The content ranges from 0 to 1.00%.

[0165] In some preferred embodiments of the present invention, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass is expressed in terms of the molar percentage of each component in the composition, and the composition of the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass satisfies:

[0166] The value of A is calculated based on the following formula (1), and the value of A is less than or equal to 0.18, and the preferred value of A is 0.05 to 0.15.

[0167] (1) A = 0.65 × Al 2 O3 +3.5×ZrO 2 -0.8×Na 2 O-2.5×B 2 O 3 ;

[0168] and / or,

[0169] The value of B is calculated based on the following formula (2), and the value of B is less than or equal to 0.80, and the preferred value of B is 0.60 to 0.78.

[0170] (2) B = 3.8 × Na 2 O+B 2 O 3 +4.5×MgO+6.0×ZnO-0.4×Al 2 O 3 -SiO 2 .

[0171] The inventors have discovered through experimental studies that the A value calculated based on the above formula is closely related to the melting effect of the substrate glass used to prepare the strengthened glass-ceramics or chemically strengthened glass-ceramics. By controlling the A value within an appropriate range through the specific proportional relationship of the above-mentioned oxide components, it can be ensured that a transparent substrate glass that meets the requirements is obtained, and that the oxide components in the substrate glass are completely melted without any unmelted components.

[0172] The inventors have also discovered through experiments that the B value calculated based on the above formula is closely related to the melting effect of the substrate glass used to prepare the strengthened microcrystalline glass or chemically strengthened microcrystalline glass. By controlling B within an appropriate range through the specific proportion of the above-mentioned oxide components, it can be ensured that the substrate glass will not be ceramicized during the preparation process, especially during the annealing process, thereby ensuring that a transparent substrate glass that meets the requirements is obtained.

[0173] In some embodiments, the A value may be 0.07-0.15, 0.09-0.15, 0.11-0.15, 0.13-0.15, 0.05-0.13, 0.05-0.11, 0.05-0.09 or 0.05-0.07. In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass of the present invention may include an A value of 0.05, 0.07, 0.09, 0.11, 0.13, 0.15, 0.17 or 0.18, or an A value within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the glass with the desired performance of the present invention can be obtained.

[0174] In some embodiments, the B value may be 0.60-0.76, 0.60-0.74, 0.60-0.72, 0.60-0.70, 0.60-0.68, 0.60-0.64, 0.62-0.78, 0.64-0.78, 0.66-0.78, 0.68-0.78, 0.70-0.78, 0.72-0.78 or 0.74-0.78. In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass of the present invention may include a B value of 0.60, 0.62, 0.64, 0.66, 0.68, 0.70, 0.72, 0.74, 0.76, 0.78 or 0.80, or a B value within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the glass with the desired properties of the present invention can be obtained.

[0175] In some preferred embodiments of the present invention, in the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass of the present invention, Al 2 O 3 The molar percentages of the components of Al, MgO, and ZnO satisfy the following relationship: 2 O 3 The molar percentage of Al minus the molar percentage of MgO and the molar percentage of ZnO is 8.00-15.00%, that is, 2 O 3 The value of -MgO-ZnO is 8.00 to 15.00%. 2 O 3 , MgO, and ZnO are the main components of the main crystal phase spinel crystal of the present invention. 2 O 3 The content relationship of MgO and ZnO can ensure the acquisition of microcrystalline glass with high crystal content / crystallinity, which is beneficial to improve the intrinsic strength of microcrystalline glass. On the other hand, by making the appropriate amount of Al 2 O 3 Remain in the residual glass phase to form [AlO 4 ] tetrahedral structure, which is also more conducive to the chemical strengthening of microcrystalline glass and the strengthening of microcrystalline glass to obtain high stress characteristics, because [AlO 4 ]The volume of the tetrahedron is larger than that of [SiO 4 ], appropriate amount

[0176] [AlO 4 ] is more conducive to broadening the ion exchange channels and promoting the diffusion of alkali metal ions.

[0177] In some embodiments, Al 2O 3 The value of -MgO-ZnO can be 8.50-15.00%, 9.00-15.00%, 9.50-15.00%, 10.00-15.00%, 10.50-15%, 11.00-15.00%, 11.50-15.00%, 12.00-15.00%, 12.50-15%, 13.00-15.00%, 13.50-15.00%, 14.0 0-15.00%, 8.00-14.50%, 8.00-14.00%, 8.00-13.50%, 8.00-13.00%, 8.00-12.50%, 8.00-12.00%, 8.00-11.50%, 8.00-11.00%, 8.00-10.50%, 8.00-10.00%, 8.00-9.50% or 8.00-9.00%. In some embodiments, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass of the present invention may contain Al 2 O 3 The value of -MgO-ZnO can be 8.00%, 8.50%, 9.00%, 9.50%, 10.00%, 10.50%, 11.00%, 11.50%, 12.00%, 12.50%, 13.00%, 13.50%, 14.00%, 14.50% or 15.00%, or within a numerical range consisting of any two of the above specific values ​​as endpoints. 2 O 3 - Value of MgO-ZnO It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired properties of the present invention can be obtained.

[0178] In another preferred embodiment of the present invention, the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass is expressed in terms of the molar percentage of each component in the composition, and the composition of the tensile stress layer of the strengthened glass-ceramics or the chemically strengthened glass-ceramics or the substrate glass satisfies:

[0179] The value of X is calculated based on the following formula (3), and the value of X is 30.00 to 50.00%, preferably 34.00 to 46.00%.

[0180] (3)X=2.1×(Al 2 O 3 -MgO-ZnO) / (SiO 2 +Al 2 O 3 -MgO-ZnO+Na 2 O+K 2 O+B 2 O3 );

[0181] and / or,

[0182] The value of Y is calculated based on the following formula (4), and the value of Y is 60.00 to 80.00%, preferably 60.00 to 75.00%.

[0183] (4)Y=(2.7×Na 2 O+1.8×(Al 2 O 3 -MgO-ZnO)) / (SiO 2 +Al 2 O 3 -MgO-ZnO+Na 2 O

[0184] +K 2 O+B 2 O 3 ).

[0185] The inventors have found through experimental studies that the X value calculated based on the above formula is closely related to the deep stress characteristics of the strengthened microcrystalline glass with excellent anti-drop performance. By controlling the X value within an appropriate range through the specific proportional relationship of the above-mentioned oxide components, it can be ensured that the strengthened microcrystalline glass prepared by the chemically strengthened microcrystalline glass of the present invention obtains excellent deep stress characteristics, such as high CS_50, DOL_O, |CT_AV|, |CT_CV|, and CT_LD values.

[0186] The inventors have also found through experimental research that the Y value calculated based on the above formula is closely related to the surface stress characteristics of the strengthened microcrystalline glass with excellent anti-drop performance. By controlling the Y value within a suitable range through the specific ratio of the above oxide components, it can be ensured that the strengthened microcrystalline glass prepared by the chemically strengthened microcrystalline glass of the present invention obtains excellent surface stress characteristics, such as obtaining a high surface K 2 O concentration, high surface CS value.

[0187] In some embodiments, the value of X can be 32.00-50.00%, 34.00-50.00%, 36.00-50.00%, 38.00-50.00%, 40.00-50.00%, 42.00-50.00%, 44.00-50.00%, 46.00-50.00%, 30.00-48.00%, 30.00-46.00%, 30.00-44.00%, 30.00-42.00%, 30.00-40.00%, 30.00-38.00%, 30.00-36.00%, or 30.00-34.00%. In some embodiments, the strengthened glass-ceramics or chemically strengthened glass-ceramics or substrate glass of the present invention may include an X value of 30.00%, 32.00%, 34.00%, 36.00%, 38.00%, 40.00%, 42.00%, 44.00%, 46.00%, 48.00% or 50.00%, or an X value within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired performance of the present invention can be obtained.

[0188] In some embodiments, the Y value can be 62.00-80.00%, 64.00-80.00%, 66.00-80.00%, 68.00-80.00%, 70.00-80.00%, 72.00-80.00%. 74.00-80.00%, 76.00-80.00%, 60.00-78.00%, 60.00-76.00%, 60.00-74.00%, 60.00-72.00%, 60.00-70.00%, 60.00-68.00%, 60.00-66.00% or 60.00-64.00%. In some embodiments, the strengthened glass-ceramics or chemically strengthened glass-ceramics or substrate glass of the present invention may include a Y value of 60.00%, 62.00%, 64.00%, 66.00%, 68.00%, 70.00%, 72.00%, 74.00%, 76.00%, 78.00% or 80.00%, or a Y value within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired performance of the present invention can be obtained.

[0189] In some preferred embodiments of the present invention, the spinel crystal of the present invention is a zinc-magnesium spinel solid solution (Zn, Mg)Al 2 O 4, that is, the main crystalline phase of the strengthened microcrystalline glass or chemically strengthened microcrystalline glass of the present invention is (Zn, Mg)Al 2 O 4 ; and / or, the strengthened glass-ceramics or chemically strengthened glass-ceramics of the present invention further comprises a secondary crystalline tetragonal zirconium oxide. (Zn, Mg)Al 2 O 4 Possessing high Young's modulus and shear modulus is beneficial to improving the intrinsic strength of the chemically strengthened microcrystalline glass and strengthened microcrystalline glass of the present invention, such as making the strengthened microcrystalline glass have high hardness, strength, fracture toughness, etc.

[0190] It should be understood that the strengthened glass-ceramics of the present invention is obtained by chemically strengthening the above-mentioned chemically strengthened glass-ceramics provided by the present invention, and the main crystalline phase of the chemically strengthened glass-ceramics of the present invention is (Zn, Mg)Al 2 O 4 , the secondary crystalline phase includes tetragonal ZrO 2 The crystal phase does not contain alkali metals and does not participate in ion exchange, so the crystal phase composition does not change basically before and after strengthening, and the optical properties of the microcrystalline glass, such as transmittance and optical b value, also do not change basically.

[0191] In some preferred embodiments of the present invention, the strengthened glass-ceramics or chemically strengthened glass-ceramics of the present invention have good crystallinity, for example, the crystallinity of the strengthened glass-ceramics or chemically strengthened glass-ceramics is above 20wt%; preferably, the crystallinity is 20.00-50.00wt%; further preferably, the crystallinity is 30.00-50.00wt%; more preferably, the crystallinity is preferably 35-45wt%. High crystallinity / crystal content can give the glass-ceramics higher intrinsic strength, so that the chemically strengthened microcrystals of the present invention have excellent mechanical properties.

[0192] In some embodiments, the crystallinity of the strengthened glass-ceramics or chemically strengthened glass-ceramics of the present invention may be 22.00-50.00wt%, 24.00-50.00wt%, 26.00-50.00wt%, 28.00-50.00wt%, 30.00-50.00wt%, 32.00-50.00wt%, 34.00-50.00wt%, 36.00-50.00wt%, 38.00-50.00wt%, 40.00-50.00wt%, 42.00-50.00wt%, 44.00-50.00wt%. wt%, 46.00~50.00wt%, 20.00~48.00wt%, 20.00~46.00wt%, 20.00~44.00wt%, 20.00~42.00wt%, 20.00~40.00wt%, 20.00~38.00wt %, 20.00~36.00wt%, 20.00~34.00wt%, 20.00~32.00wt%, 20.00~30.00wt%, 20.00~28.00wt%, 20.00~26.00wt% or 20.00~24.00wt%. In some embodiments, the strengthened glass-ceramics or chemically strengthened glass-ceramics of the present invention may include a crystallinity value of 20.00wt%, 22.00wt%, 24.00wt%, 26.00wt%, 28.00wt%, 30.00wt%, 32.00wt%, 34.00wt%, 36.00wt%, 38.00wt%, 40.00wt%, 42.00%, 44.00wt%, 46.00wt%, 48.00wt% or 50.00wt%, or a crystallinity value within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired performance of the present invention can be obtained.

[0193] In some preferred embodiments of the present invention, in the above-mentioned strengthened glass-ceramics or chemically strengthened glass-ceramics of the present invention, the average grain size is ≤15.0nm, preferably 1.0 to 15.0nm, more preferably 1.0 to 10.0nm, and more preferably 4.5 to 8.0nm. The appropriate grain size is conducive to achieving excellent optical effects of the glass-ceramics.

[0194] In some embodiments, the average grain size of the strengthened glass-ceramics or chemically strengthened glass-ceramics of the present invention may be 1.0-13.0 nm, 1.0-11.0 nm, 1.0-9.0 nm, 1.0-7.0 nm, 1.0-5.0 nm, 1.0-3.0 nm, 3.0-15.0 nm, 3.0-13.0 nm, 3.0-11.0 nm, 3.0-9.0 nm, 3.0-7.0 nm or 3.0-5.0 nm. In some embodiments, the strengthened glass-ceramics or chemically strengthened glass-ceramics of the present invention may include an average grain size value of 1.0 nm, 3.0 nm, 4.5 nm, 5.0 nm, 7.0 nm, 8.0 nm, 9.0 nm, 11.0 nm, 13.0 nm or 15.0 nm, or an average grain size value within a numerical range consisting of any two of the above specific numerical values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the glass with the desired properties of the present invention can be obtained.

[0195] In another preferred embodiment of the present invention, the above-mentioned strengthened glass-ceramics or chemically strengthened glass-ceramics of the present invention exhibits high transparency in the visible light range (that is, the strengthened glass-ceramics with excellent drop resistance is transparent). Strengthened glass-ceramics or chemically strengthened glass-ceramics exhibit high transmittance in the visible light range. For example, the above-mentioned chemically strengthened glass-ceramics, at a thickness of 0.7 mm, for light with a wavelength of 550 nm, the transmittance of the chemically strengthened glass-ceramics is greater than or equal to 85%, and preferably the transmittance is greater than or equal to 89%.

[0196] In some embodiments, at a thickness of 0.7 mm, for light with a wavelength of 550 nm, the transmittance of the strengthened glass-ceramics or chemically strengthened glass-ceramics of the present invention may be 89.0%, 89.5%, 90.0%, 90.5% or 91.0%, or a transmittance within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the glass with the desired performance of the present invention can be obtained.

[0197] In some preferred embodiments of the present invention, the Young's modulus of the above-mentioned strengthened glass-ceramics or chemically strengthened glass-ceramics of the present invention is ≥100GPa, preferably ≥110GPa, and more preferably 114GPa≤Young's modulus≤140GPa. It should be understood that in the present invention, after chemical strengthening treatment, the Young's modulus of the chemically strengthened glass-ceramics will increase appropriately, that is, the Young's modulus of the strengthened glass-ceramics will be greater than or equal to the chemically strengthened glass-ceramics.

[0198] In some embodiments, the Young's modulus of the strengthened glass-ceramics or chemically strengthened glass-ceramics of the present invention can be 114-140 GPa, 114-138 GPa, 114-136 GPa, 114-134 GPa, 114-132 GPa, 114-130 GPa, 114-128 GPa, 114-126 GPa, 116-140 GPa, 118-140 GPa, 120-140 GPa, 122-140 GPa, 124-140 GPa, 126-140 GPa or 128-140 GPa. In some embodiments, the Young's modulus of the strengthened glass-ceramics or chemically strengthened glass-ceramics of the present invention may be 100 GPa, 114 GPa, 116 GPa, 118 GPa, 120 GPa, 122 GPa, 240 GPa, 126 GPa, 128 GPa, 130 GPa, 135 GPa or 140 GPa, or a Young's modulus value within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired performance of the present invention can be obtained.

[0199] In some preferred embodiments of the present invention, the optical b value of the strengthened glass-ceramics or chemically strengthened glass-ceramics of the present invention is 0.20 to 1.50, preferably 0.50 to 1.20, at a thickness of 0.7 mm.

[0200] In some embodiments, at a thickness of 0.7 mm, the optical b value of the above-mentioned strengthened microcrystalline glass or chemically strengthened microcrystalline glass of the present invention can be 0.20-1.40, 0.20-1.30, 0.20-1.20, 0.20-1.10, 0.20-1.00, 0.20-0.90, 0.20-0.80, 0.20-0.70, 0.20-0.40, 0.30-1.50, 0.40-1.50, 0.50-1.50, 0.60-1.50, 0.70-1.50, 0.80-1.50, 0.90-1.50, 1.00-1.50 or 1.10-1.50. In some embodiments, the optical b value of the strengthened glass-ceramics or chemically strengthened glass-ceramics of the present invention may be 0.20, 0.30, 0.40, 0.50, 0.60, 0.70, 0.80, 0.90, 1.00, 1.10, 1.20, 1.30, 1.40 or 1.50, or an optical b value within a numerical range consisting of any two of the above specific values ​​as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired performance of the present invention can be obtained.

[0201] In a third aspect, the chemically strengthened glass-ceramics can be produced and manufactured by the following method: heat-treating a substrate glass to form the chemically strengthened glass-ceramics; the chemically strengthened glass-ceramics contains spinel crystals, and the spinel crystals are the main crystalline phase of the chemically strengthened glass-ceramics;

[0202] The chemically strengthened glass-ceramics contains the following oxides in mol%: SiO 2 38.00~48.00%,Al 2 O 3 25.50~30.00%, ZrO 2 3.00~5.00%, MgO 5.00~8.00%, ZnO 8.00~14.00%, Na 2 O 7.20~14.00%, B 2 O 3 3.00~8.00%, K 2 O 0~2.00% and Y 2 O 3 0~1.00%;

[0203] Wherein, the chemically strengthened glass-ceramics contains substantially no Li 2 O, in mol%, Li 2 O is less than 0.01%.

[0204] Exemplarily, the method for preparing the chemically strengthened glass-ceramics of the present invention may include the following steps:

[0205] (1) Preparation of substrate glass: The substrate glass contains the following oxides in mol% ratio: SiO 2 38.00~48.00%,Al 2 O 3 25.50~30.00%, ZrO 2 3.00~5.00%, MgO 5.00~8.00%, ZnO8.00~14.00%, Na 2 O 7.20~14.00%, B 2 O 3 3.00~8.00%, K 2 O 0~2.00% and Y 2 O 3 0~1.00%; wherein the substrate glass substantially does not contain Li 2 O, in mol%, Li 2 O is less than 0.01%;

[0206] (2) Preparation of chemically strengthened glass-ceramics: The substrate glass obtained in step (1) is heat-treated to obtain chemically strengthened glass-ceramics.

[0207] In the present invention, the forming method of the substrate glass includes but is not limited to float, overflow, rolling or casting process. Exemplarily, the components are mixed evenly according to the formula, melted and formed, and then cooled and annealed to obtain the substrate glass. Preferably, the mixed raw materials are placed in an electric furnace or a gas furnace and melted at a melting temperature of 1250°C to 1650°C, more preferably at a melting temperature of 1480°C to

[0208] 1650℃, melting time is 5 to 24 hours; after the melting process is completed, the glass liquid is cast into a mold for molding, and after cooling to 850℃ to 1000℃, preferably, it is placed in an annealing furnace for annealing at a temperature of 500℃ to 650℃, and the annealing is kept warm for 12 to 48 hours.

[0209] The heat treatment in step (2) may include a nucleation treatment and / or a crystallization treatment, and preferably a nucleation treatment and a crystallization treatment are used.

[0210] In order to obtain the desired physical properties of the chemically strengthened glass-ceramics, the substrate glass can be heat treated in one step or in two or more steps. If a one-step heat treatment is performed, it means that the nucleation treatment is not performed separately, and the nucleation and target crystal growth are directly performed in a one-step heating process, which can be understood as a direct crystallization treatment. If a two-step heat treatment is performed, it means that a two-step heating process is performed, first a nucleation treatment, i.e., a nucleation treatment, is performed, and then a target crystal growth treatment, i.e., a crystallization treatment, is performed.

[0211] It should be understood that in the present invention, the nucleation treatment is to increase the temperature to a prescribed nucleation treatment temperature (also called nucleation temperature), and after reaching the nucleation treatment temperature, maintain the temperature for a certain time (i.e., nucleation treatment time, also called nucleation time). The crystallization treatment is to increase the temperature to a prescribed crystallization treatment temperature (also called crystallization temperature), and after reaching the crystallization treatment temperature, maintain the temperature for a certain time (i.e., crystallization treatment time, also called crystallization time).

[0212] In order to make the chemically strengthened glass-ceramics precipitate the desired crystal phase and obtain the desired physical and chemical properties, the preferred heat treatment process of the present invention is:

[0213] The nucleation temperature is preferably 600-850° C., and the nucleation treatment time can be 0-72 h, preferably 0-24 h; the crystallization treatment temperature is 700-1000° C., and the crystallization treatment time is 0.1-72 h, preferably 0.1-24 h.

[0214] It is worth mentioning that the inventors found through a large number of experiments that due to the optimization of the formula of the present invention, the desired target microcrystalline glass can be prepared at a heat treatment temperature lower than that of the existing scheme. Therefore, in the present invention, the temperature of the nucleation treatment may be preferably 600-750°C; the temperature of the crystallization treatment may be preferably 700-800°C, which is more conducive to improving the mass production performance of microcrystalline glass and is more in line with the industry's development needs of energy conservation and carbon reduction.

[0215] In some preferred embodiments of the present invention, a two-step temperature rise heat treatment method is used to prepare the chemically strengthened microcrystalline glass, that is, the substrate glass is subjected to a nucleation treatment and a crystallization treatment in sequence to prepare the microcrystalline glass. In some embodiments, when the temperature of the nucleation treatment is 600-750°C, the nucleation treatment time is preferably 60-360 minutes, and the nucleation time is more preferably 100-300 minutes; and / or, when the temperature of the crystallization treatment is 700-800°C, the crystallization time is preferably 60-360 minutes, and the crystallization time is more preferably 100-300 minutes.

[0216] In some preferred embodiments of the present invention, during the heat treatment, the heating rate is controlled to be 5 to

[0217] 15K / min, preferably 10K / min. It should be understood that the heating rate here includes the heating rate from room temperature to nucleation temperature and the heating rate from nucleation temperature to crystallization temperature.

[0218] In some preferred embodiments of the present invention, the composition of the substrate glass of the present invention satisfies the following conditions, based on the content expressed as a molar percentage of each oxide in the substrate glass composition:

[0219] A=0.65×Al 2 O 3 +3.5×ZrO 2 -0.8×Na 2 O-2.5×B 2 O 3 , A≤0.18, preferably the value of A is 0.05 to 0.15;

[0220] and / or, B = 3.8 × Na 2 O+B 2 O 3 +4.5×MgO+6.0×ZnO-0.4×Al 2 O 3 -SiO 2 , B≤

[0221] 0.80, preferably the value of B is 0.60 to 0.78;

[0222] and / or, X = 2.1 × (Al 2 O 3 -MgO-ZnO) / (SiO 2 +Al 2 O 3 -MgO-ZnO+Na 2 O+K 2 O+B 2 O 3 ), X = 30.00-50.00%, preferably X = 34.00-46.00%;

[0223] And / or, Y = (2.7 × Na 2 O+1.8×(Al 2 O 3 -MgO-ZnO)) / (SiO 2 +Al 2 O 3 -MgO-ZnO+Na 2 O+K 2 O+B 2 O 3 ), Y = 60.00-80.00%, preferably Y = 60.00-75.00%;

[0224] And / or, in the substrate glass, Al 2 O 3 The molar percentages of the components of Al, MgO, and ZnO satisfy the following relationship: 2 O 3 -MgO-ZnO=8.00~15.00%.

[0225] In some preferred embodiments of the present invention, the substrate glass substantially does not contain BaO, and the BaO content is less than 0.01% by mol%; and / or the substrate glass substantially does not contain TiO 2 , in mol%, TiO 2 Less than 0.01%.

[0226] In the present invention, the chemically strengthened microcrystalline glass obtained in the above step (2) can be cold-processed as needed. The cold-processing treatment is to process the microcrystalline glass into microcrystalline glass samples. For example, the microcrystalline glass is processed into a polished sheet of a desired size by one or more methods of slicing, grinding, and polishing, such as a polished sheet with a length, width, and thickness of 50 mm×50 mm×0.7 mm.

[0227] In the present invention, those skilled in the art can select the thickness of the chemically strengthened glass-ceramics according to the requirements. Exemplarily, the thickness of the chemically strengthened glass-ceramics is 0.2-5.0 mm.

[0228] In the present invention, when preparing the substrate glass, a clarifier may be added to the raw materials for preparing the substrate glass, and the clarifier includes but is not limited to the raw materials for preparing the substrate glass in the above-mentioned step of preparing the substrate glass further including a clarifier, and the clarifier includes but is not limited to NaCl, Na 2 SO4、SnO 2 , As 2 O 3 , Sb 2 O 3 , NaNO 3 , KNO 3 , CeO 2 and (NH 4 ) 2 SO 4 One or more of; preferably NaCl, SnO 2 , NaNO 3 and CeO 2 Based on the total weight of the raw materials of the substrate glass, the amount of the clarifier added is 0.01wt% to 2.00wt%, preferably 0.01wt% to 1.50wt%.

[0229] In a fourth aspect, the present invention further provides a method for preparing a strengthened glass-ceramic, comprising the following steps: subjecting the above-mentioned chemically strengthened glass-ceramic to chemical strengthening treatment to obtain the above-mentioned strengthened glass-ceramic, wherein the strengthened glass-ceramic contains spinel crystals, and the spinel crystals are the main crystalline phase of the strengthened glass-ceramic; the composition of the strengthened glass-ceramic does not substantially contain Li 2 O, in mol%, Li 2 O is less than 0.01%; the strengthened microcrystalline glass satisfies: CS_50≥100MPa, |CT_AV|≥70MPa, DOL_0≥0.13t, t is the thickness of the microcrystalline glass.

[0230] In the present invention, the chemical strengthening treatment includes a single-step strengthening method or a multi-step strengthening method; and the salt bath for the chemical strengthening treatment is a molten salt containing a potassium salt.

[0231] In some embodiments, the chemically strengthened glass-ceramics may be processed into sheets and / or shaped (such as punching, hot bending, etc.), polished and / or swept after shaping, and then chemically strengthened through a chemical strengthening process.

[0232] The chemical strengthening treatment described in the present invention is an ion exchange method. During the ion exchange process, the smaller alkali metal ions in the chemically strengthened glass-ceramics are replaced or "exchanged" by larger alkali metal ions of the same valence state near the glass-ceramics, and the larger ions replace the smaller ions, thereby constructing a compressive stress layer in the glass. The ion exchange strengthening method can be carried out in multiple steps, such as two steps, or in a single step. Ion exchange is carried out by immersing the chemically strengthened glass-ceramics in a salt bath of at least one molten salt containing larger alkali metal ions, so that the larger alkali metal ions in the salt bath are used to replace the smaller alkali metal ions in the glass-ceramics. Alternatively, other monovalent metal ions such as Ag + , Tl + , Cu + etc. can also be used to exchange monovalent ions. The ion exchange process may include, but is not limited to, immersing it in a single salt bath, or immersing it in multiple salt baths of the same or different compositions, with washing and / or annealing steps between immersions.

[0233] In some embodiments, the above-mentioned chemically strengthened glass-ceramics of the present invention can be immersed in a salt bath containing potassium salt for chemical strengthening treatment. In some embodiments, the temperature of the salt bath for chemical strengthening treatment is 380°C to 600°C, preferably 400°C to 550°C. Exemplarily, the chemically strengthened glass-ceramics can be immersed in a salt bath containing molten potassium salt (such as one or more of potassium nitrate, potassium sulfate, potassium carbonate, preferably potassium nitrate) at a temperature of 380°C to 600°C for about 4 to 48 hours for ion exchange, preferably the temperature range of the salt bath is 400°C to 550°C, more preferably the temperature of the salt bath is 450°C to 530°C, and the preferred ion exchange / chemical strengthening time range is 9 to 48 hours.

[0234] In some preferred embodiments of the present invention, the concentration of potassium salt in the salt bath for chemical strengthening treatment is 60wt% to 100wt%. For example, the salt bath containing potassium salt can be 100wt% potassium nitrate, or a mixed salt of potassium nitrate and sodium nitrate, and the concentration of potassium nitrate in the mixed salt is greater than or equal to 60wt% and less than 100wt%. In addition, according to the need, 0-1wt% LiNO 3 .

[0235] In the present invention, through a chemical strengthening treatment step, K ions in the salt bath replace part of the Na ions in the chemically strengthened microcrystalline glass, thereby forming a compressive stress layer on the glass surface to obtain strengthened microcrystalline glass, so that the chemically strengthened microcrystalline glass achieves a specific stress distribution structure, giving the chemically strengthened microcrystalline glass specific and excellent surface stress characteristics and deep stress characteristics, thereby giving it high mechanical properties.

[0236] In some embodiments, before the chemical strengthening treatment, the chemically strengthened glass-ceramics may be preheated at 300 to 400° C. as required, and the preheating time is preferably 10 to 30 minutes.

[0237] In some embodiments, a thermal migration process at 350-500° C. may be performed between multiple strengthening steps as needed, and the thermal migration time is preferably 15-120 min.

[0238] In some embodiments, in the single-step strengthening or multi-step strengthening, after continuously strengthening multiple batches of samples in each salt bath, when the surface CS of a batch of samples drops to 10-20% of the initial batch, the glass strengthening in the salt bath is stopped, and the salt bath needs to be cleaned or replaced for glass strengthening.

[0239] In a fifth aspect, the above-mentioned strengthened microcrystalline glass or the above-mentioned chemically strengthened microcrystalline glass or the above-mentioned substrate glass for preparing chemically strengthened microcrystalline glass provided by the present invention can be applied to mobile phone displays, tablet computer displays, handheld game consoles, electronic terminals, portable digital devices, vehicle central control screens, electronic whiteboard glass, smart home touch screens, vehicle windshields, aircraft windshields or aircraft windshields.

[0240] The following describes in detail how to prepare a tempered microcrystalline glass with excellent anti-drop performance and the beneficial effects achieved through examples and comparative examples.

[0241] 1: Specific operation examples

[0242] Example 1

[0243] According to the component proportions of glass formula 1 of Example 1 in Table 1, various raw materials (conventional industrial raw materials) were configured in a platinum crucible, with a total amount of 1000 g of raw materials configured, and then mixed in a V-type mixer for 30 minutes. After mixing, 5 g of clarifier NaCl was added, and then the raw materials were transferred to a platinum crucible, and then melted in a 1650°C lifting furnace (lifting furnace model: SJF1750, manufacturer: Nanjing Boyuntong Instrument Technology Co., Ltd.) for 5 hours, and then poured into a stainless steel mold preheated at 300°C (usually preheated to 200-400°C) for molding and cooling, cooled to 900°C, and then placed in a 600°C annealing furnace for annealing for 24 hours, and then cooled to room temperature with the furnace to obtain the substrate glass.

[0244] The substrate glass is heat treated in a resistance furnace (equipment model: SLX1400-40, manufacturer: Shanghai Shengli Testing Instrument Co., Ltd.), and the heat treatment process (nucleation temperature / nucleation time, crystallization temperature / nucleation time, and heating rate during heat treatment) is carried out according to Table 1 to obtain a sample of microcrystalline glass for chemical strengthening. The microcrystalline glass sample is cut, CNC processed (computer numerical control, i.e., numerical control machine tool, the CNC instrument model used in the present invention is: RCG500S), and polished to obtain the mirror-smooth microcrystalline glass sheet. In the present invention, the processed microcrystalline glass sheet has a specification of 50mm×50mm×0.7mm in length, width, and thickness.

[0245] The physical properties of the prepared glass-ceramics were tested according to the following method:

[0246] Young's modulus test: The Young's modulus of the sample was obtained by ultrasonic testing, and the instrument was UMS-100 ultrasonic material characterization system.

[0247] XRD test: The microcrystalline glass sheet is ground into glass fine powder with a grinding machine, and its particle size is less than 75μm, and then it is tested by an X-ray diffractometer (Shimadzu's XRD-6100) to obtain an XRD diffraction peak curve. The X-ray diffractometer used in the present invention is Shimadzu's XRD-6100, the target material is copper, the test incident angle range is 2θ=10-80°, the scanning speed is 0.2° / min, the working voltage is 40kV, and the working current is 30mA. The XRD diffraction data is analyzed by JADE software to obtain the crystal phase of the sample.

[0248] Average grain size: The average grain size of the sample can be calculated using the result data obtained by XRD test according to the Scherrer formula D = Kλ / (βcosθ), where λ is the X-ray wavelength, λ is 0.154056nm, β is the half-height width of the diffraction peak, K = 0.89, and θ is the Bragg diffraction angle. Specifically, the RAW file (diffraction spectrum) output by the XRD instrument is curve-fitted in the Jade software, and Jade outputs a fitting report. According to the angle 2θ value and Peak FWHM value (half-height width of the diffraction peak) corresponding to each diffraction peak in the fitting report, and the Peak FWHM value is converted into radian β = (FWHM / 180*3.14), the grain size of each diffraction peak is calculated by D = Kλ / (βcosθ) and then averaged to obtain the average grain size.

[0249] Testing method for crystal content / crystallinity: Import the X-ray diffractometer test result file (RAW format) into the X-ray diffraction data Rietveld refinement software (such as Gsas, Fullprof, Maud), perform fitting and calculation, and then obtain the crystal content / crystallinity in the microcrystalline glass sample. The ratio of the fitted crystal phase peak area to the fitted total peak area is the crystal content, which is also referred to as crystallinity in the present invention.

[0250] b value determination: The b value was obtained by testing the sample using a Konica Minolta spectrophotometer CM-3600A from Japan, and the average value of 5 parallel samples was taken as the b value result of the sample to be tested.

[0251] Transmittance determination: Test according to GB / T 7962.12-2010 Test Method for Colorless Optical Glass Part 12: Spectral Transmittance. First, clean the glass-ceramic sample in an ultrasonic cleaner. The cleaning conditions are: cleaning time 5-10 minutes; cleaning agent used: commonly used detergent diluted 10 times; cleaning temperature: 45℃-65℃; cleaning frequency: 20KHZ-40KHZ. Then use a haze meter (Japan Konica Minolta spectrophotometer CM-3600A) to test its transmittance under different wavelengths of light.

[0252] The transmittance of the sample under 550nm wavelength light was measured using a Konica Minolta spectrophotometer CM-3600A from Japan, and the average value of 5 parallel samples was taken as the transmittance result of the sample to be tested under 550nm wavelength light.

[0253] Thickness of glass: Determined by micrometer test. It should be understood that in the thickness direction, the degree of ion exchange changes gradually from the surface to the center, and the total Na-K and / or Li-Na exchange amount generally does not exceed 1% of the total mass of the sample, and the difference in ion radius is at the pm level, so the expansion effect in the thickness direction is very slight, and it can be approximately considered that the thickness has basically not changed. That is, the thickness change of microcrystalline glass before and after chemical strengthening is very small and can be ignored.

[0254] Density determination: The density of the glass-ceramic sample is tested according to the principle of the “Archimedes drainage method”. The testing instrument used in the present invention is an ALFA MIRAGE electronic density balance SD-200L.

[0255] After completing the above-mentioned performance tests, the 0.7 mm thick microcrystalline glass sample obtained above is then chemically strengthened according to the mixed or single molten salt composition, ion exchange step temperature and ion exchange time conditions shown in Table 2 to obtain strengthened microcrystalline glass.

[0256] The sample is subjected to single-step strengthening, and the specific process is as follows:

[0257] IOX (ion exchange): 480°C × 100% KNO3 × 24h (refers to exchange in 100wt% KNO3 molten salt at 480°C for 24h; similar expressions in this article have similar meanings, and the molten salt temperature, composition, and ion exchange time used for ion exchange are abbreviated in this form);

[0258] The physical properties of the prepared strengthened glass-ceramics were tested according to the following method:

[0259] In the present invention, CS_50, |CT_CV|, |CT_AV|, and DOL_0 are tested using the stress meter SLP-2000 of Japan Luceo (Japan Orihara). The test conditions are: light source wavelength is 518nm, SOC=25.5 (nm / cm) / MPa, refractive index=1.60, and exposure time: 300usec. When testing CS_50, |CT_CV|, |CT_AV|, and DOL_0, it is necessary to first drip its special refractive liquid on the stress meter, then wipe the strengthened microcrystalline glass product clean, and place it on the test path to test its stress value. The refractive index of the refractive liquid used for SLP-2000 is 1.51. Unless otherwise specified, the above-mentioned test conditions are used when testing the stress values ​​in the embodiments and comparative examples of the present invention. It should be noted that when testing the stress values ​​of comparative examples 10-15, the photoelastic constant was set to 25.5 and the refractive index nd was 1.6; when testing the stress value of comparative example 7, the photoelastic constant was set to 25.5 and the refractive index nd was 1.54; when testing the stress value of comparative example 8, the photoelastic constant was set to 28.6 and the refractive index nd was 1.51.

[0260] The tensile stress line density CT_LD is related to the thickness of the glass sheet, the strengthening depth and the average tensile stress, and can be used to evaluate the drop resistance of the glass sheet. In the present invention, the CT_LD is calculated according to the following formula:

[0261]

[0262] Where t represents the thickness of the glass-ceramic sheet (the glass thickness in the following embodiments and comparative examples of the present invention is 0.7 mm), in mm; DOL_0 represents the depth of the compressive stress layer, in μm; CT_AV represents the internal average tensile stress, and its absolute value is taken in the calculation, in MPa. It should be understood that in the calculation formula of the tensile stress linear density, the data is substituted into the calculation according to the above unit requirements, and the calculation result is obtained, and the unit does not participate in the calculation.

[0263] The calculation method of the exchange amount is: the ratio of the mass difference of the microcrystalline glass sheet before and after chemical strengthening to the mass of the microcrystalline glass sheet before chemical strengthening.

[0264] Surface K 2 O concentration test: In the present invention, K 2 The O concentration was measured by X-ray fluorescence spectrometer (XRF). The equipment model used was (Thermo Scientific ARL PERFORM'X), the target material was Rh (rhodium), the light tube voltage was 40kW, the current was 60mA, the collimator was 0.15, the crystal was LiF200, the detector was FPC, the test range was 29mm circle, and the analysis software was UniQuant standardless analysis.

[0265] Vickers hardness (HV) test: The chemically strengthened strengthened microcrystalline glass is made into a small piece with a length, width and thickness of 50mm*50mm*0.7mm, and a glass sample with a clean surface and no visible scratches, pits, cracks and other damage is selected as a test sample, and then the Vickers hardness is measured using a Vickers hardness tester. The Vickers hardness tester used in the present invention is a digital display small load Vickers hardness tester (Beijing Kewei Technology Co., Ltd., VTD405). Test conditions: load 300gf, load time 10s, the effectiveness of the indentation complies with the "GB / T37900-2019 Ultra-thin glass hardness and fracture toughness test method small load Vickers hardness indentation method" standard. Select 3 different positions on the same sample surface for measurement, and select the average value of the 3 measurement results as the Vickers hardness result of the glass sample to be tested.

[0266] Fracture toughness test: Tested according to GB / T 37900-2019 Ultra-thin glass hardness and fracture toughness test method Small load Vickers hardness indentation method. Specifically, the indentation is prepared in the same way as the Vickers hardness measurement, and the crack length 2C in the diagonal direction of the indentation is measured. 1 , 2C 2 , and its maximum value cannot exceed the thickness of the glass. At least 5 effective indentation morphology measurements are performed on the surface of one sample, and the average value is calculated as the final result value of the sample.

[0267] Indentation fracture toughness calculation formula:

[0268] IFR: Indentation fracture toughness, unit is MPa·m 1 / 2 ); E: elastic modulus of the sample, in GPa; 2C 1 , 2C 2 : Crack extension length in the diagonal direction of the indentation, in millimeters (mm), d 1 , d 2 : The diagonal length of the indentation, in millimeters (mm); F: The test load value, in Newton (N).

[0269] Test method for average drop resistance height: The average sandpaper drop resistance height refers to the average value of the sandpaper drop resistance height of each sample measured in multiple identical glass samples, which can be used to characterize the drop resistance performance of microcrystalline glass. At least 10 identical glass samples are tested in each batch, and the average sandpaper drop resistance height is:

[0270]

[0271] Where n is the number of glass samples tested in each batch, hi is the sandpaper drop resistance height of a single sample test;

[0272] Among them, the test method for the sandpaper drop height of a single sample is:

[0273] Step 1: Paste 120-grit sandpaper on the lower surface of the 160g model machine, and place the model machine on the green figure LT-SKDL-CD drop machine;

[0274] Step 2: Place a glass sample to be tested with a length, width and thickness of 50mm*50mm*0.7mm directly under the model machine, with the glass sample facing the sandpaper. Make the model machine fall from a certain drop height to impact the glass sample directly under the model machine. If the glass sample does not break, the drop height of the model machine is increased according to a certain rule. For example, the drop height starts from 0.4m, and the sample is dropped once. If it does not break, increase the height by 0.1m each time and drop again until the glass sample breaks;

[0275] Step 3: The last drop height of the glass sample when it breaks is recorded as the anti-sandpaper drop height. For example, if the drop height when it breaks is 0.5m, the anti-sandpaper drop height of the sample is 0.4m.

[0276] Test method for 2.5m drop test pass rate: 2.5m drop test pass rate refers to the number of samples that pass after a drop test from a height of 2.5m divided by the total number of test samples. The percentage of passed samples is calculated. After the drop test, if the glass sample does not break, it is recorded as passed, otherwise it is recorded as failed; it is used to characterize the drop resistance of microcrystalline glass. Take at least 10 identical microcrystalline glass samples for each batch for testing.

[0277] Specifically, the method for a single sample to undergo a 2.5m drop test is as follows:

[0278] Step 1: Paste 120-grit sandpaper on the lower surface of the 160g model machine, and place the model machine on the green figure LT-SKDL-CD drop machine;

[0279] Step 2: Place a glass sample with a length, width and thickness of 50mm*50mm*0.7mm directly under the model machine, with the glass sample facing the sandpaper. Make the model machine fall once from a drop height of 2.5m to impact the glass sample directly under the model machine. If the glass sample does not break, it is recorded as passed, otherwise it is recorded as failed.

[0280] Test method for high temperature and high humidity failure time: Use QTH_80C full temperature and humidity alternating test chamber for testing, and the alternating test chamber conditions are set as follows: temperature is 85°C and relative humidity is 85%. Take out the sample every 12 hours, and wipe the glass surface with a dust-free cloth to observe whether there are spots or fog spots that cannot be wiped off. If the sample has spots or fog spots that cannot be wiped off during this observation, and the last time it was taken out for observation, the sample did not have spots or fog spots that cannot be wiped off, then the time the glass sample was taken out for this observation is used as the node, and the time the glass sample was placed in the test chamber is calculated, which is recorded as the high temperature and high humidity failure time of the test sample, which is used to characterize weather resistance.

[0281] Examples 2-5 were operated under the same operating conditions as Example 1, and corresponding tests were performed. Table 1 shows the glass formula compositions and heat treatment processes for preparing the substrate glass in Examples 1-5, as well as the performance parameters of the chemically strengthened glass-ceramics prepared therefrom; Table 2 shows the strengthening conditions of the chemically strengthened glass-ceramics in Examples 1-5 and the performance parameters of the prepared strengthened glass-ceramics.

[0282] Table 1 Base glass formula, melting state, heat treatment process and performance parameters of chemically strengthened microcrystalline glass prepared in Examples 1-5

[0283]

[0284]

[0285]

[0286] Table 2 Chemical strengthening conditions of the chemically strengthened glass-ceramics in Examples 1-5 and performance parameters of the prepared strengthened glass-ceramics

[0287]

[0288]

[0289] Note: Since the maximum time for the high temperature and high humidity failure test in the present invention is 360 hours (15 days), if the glass sample is taken out for observation after 360 hours, and the sample still has no spots and / or fog points that cannot be wiped off, it is judged that the high temperature and high humidity failure time of the glass sample is greater than 360 hours.

[0290] Examples 6-10 were operated under the same operating conditions as Example 1 and were tested accordingly. Table 3 shows the glass formula compositions and heat treatment processes for preparing the substrate glass of Examples 6-10 and the performance parameters of the chemically strengthened glass-ceramics prepared therefrom; Table 4 shows the strengthening conditions of the chemically strengthened glass-ceramics in Examples 6-10 and the performance parameters of the strengthened glass-ceramics prepared therefrom.

[0291] Table 3 Base glass formula, melting state, heat treatment process and performance parameters of chemically strengthened microcrystalline glass prepared in Examples 6-10

[0292]

[0293]

[0294] Table 4 Chemical strengthening conditions of the chemically strengthened glass-ceramics in Examples 6-10 and performance parameters of the prepared strengthened glass-ceramics

[0295]

[0296]

[0297] Note: Since the maximum time for the high temperature and high humidity failure test in the present invention is 360 hours (15 days), if the glass sample is taken out for observation after 360 hours, and the sample still has no spots and / or fog points that cannot be wiped off, it is judged that the high temperature and high humidity failure time of the glass sample is greater than 360 hours.

[0298] Examples 11-15 respectively use the same chemically strengthened glass-ceramics as Examples 1, 4, and 5, and operate under different strengthening conditions. The specific strengthening processes used and the performance parameters of the prepared strengthened glass-ceramics are shown in Table 5.

[0299] Table 5 Chemical strengthening conditions of Examples 11-15 and performance parameters of the strengthened microcrystalline glass prepared therefrom

[0300]

[0301]

[0302] Note: Since the maximum time for the high temperature and high humidity failure test in the present invention is 360 hours (15 days), if the glass sample is taken out for observation after 360 hours, and the sample still has no spots and / or fog points that cannot be wiped off, it is judged that the high temperature and high humidity failure time of the glass sample is greater than 360 hours.

[0303] Figure 1 This is a diagram showing the melting results of the substrate glass of Example 1. Figure 2This is a diagram showing the melting results of the substrate glass of Example 3. Figure 3 This is a diagram showing the melting results of the substrate glass of Example 4. Figure 4 This is an appearance diagram of the chemically strengthened glass-ceramics of Example 4. Figure 5 The appearance of the chemically strengthened glass-ceramics of Example 5 is shown in FIG. Figure 1-5 It can be seen that the base glass prepared by the glass formula of the present invention and the microcrystalline glass prepared by a specific heat treatment process are both transparent glass materials in the visible light range.

[0304] Figure 6 The thermogravimetric analysis curve of the substrate glass of Example 1 is shown in Figure 1. The thermogravimetric analysis test method is as follows: the substrate glass of Example 1 is ground and then passed through a 200-mesh sieve; the test conditions are: room temperature to 1100°C, 10°C / min heating rate; the test instrument is a Mettler-Toledo TGA / DSC3+ thermogravimetric and synchronous thermal analyzer. The obtained raw data is imported into the OriginPro software to obtain the following Figure 6 The thermogravimetric analysis curve shown below shows the endothermic peak. Figure 6 It can be seen that the first endothermic peak is 735°C; upward is the exothermic peak, and the first exothermic peak is 848°C.

[0305] Figure 7 The XRD diffraction pattern of the chemically strengthened glass-ceramics of Example 1 is as follows: Figure 7 It can be seen that the main crystalline phase of the glass-ceramics is (Zn, Mg)Al 2 O 4 (Card No.: 74-1136 and 73-1959), the secondary crystalline phase is zirconium oxide (Card No.: 80-1007).

[0306] Figure 8 is the transmittance curve of the chemically strengthened glass-ceramics of Example 5 under different wavelength conditions, Figure 8 It can be seen that the transmittance of the microcrystalline glass at a wavelength of 550 nm is greater than 90%.

[0307] From Tables 1 and 3, combined Figure 1-3 It can be seen that when the glass formula provided by the present invention is used to prepare the substrate glass, the substrate glass with good overall uniformity and transparency can be melted. At the same time, the substrate glass prepared by the present invention can be used to prepare (Zn, Mg)Al2O3 under the condition that the heat treatment temperature does not exceed 800°C. 2 O 4 The main crystal phase is tetragonal zirconia, the secondary crystal phase is tetragonal zirconia, the crystallinity is high and the optical properties are excellent. Specifically, the crystallinity of the chemically strengthened glass-ceramic of the present invention is 37.52-40.41wt%, and the Young's modulus is above 101GPa; the transmittance of the chemically strengthened glass-ceramic prepared by the present invention at a wavelength of 550nm is greater than or equal to 89%.

[0308] It can be seen from Tables 2, 4-5 that the strengthened glass-ceramics of the present invention has both excellent surface stress characteristics and excellent deep stress characteristics. Specifically, the CS_50 of the strengthened glass-ceramics of the present invention is 148.02-337.69MPa, |CT_CV| is 89.07-146.38MPa, and |CT_AV| is

[0309] 72.38-125.91MPa, DOL_0 is 108.69-132.50μm, both of which are greater than 0.13 times the glass thickness (0.7mm), CT_LD is 49620-80192MPa / mm, and the fracture toughness is 1.51-1.66MPa·m 1 / 2 , higher |CT_AV|, |CT_CV|, DOL_0, CT_LD and CS_50 indicate that the strengthened glass-ceramics has excellent deep stress; the surface K 2 O content (i.e., surface K 2 O concentration) is 9.16-15.21%. It should be understood that the K on the surface of the strengthened microcrystalline glass is mainly exchanged into the glass surface by the salt bath through the chemical strengthening process. 2 The higher the O content, the more K-Na exchange occurs during the strengthening process, and the higher the surface compressive stress of the microcrystalline glass can obtain, and the better the surface stress characteristics. The drop test results show that the average sandpaper drop height (120 mesh sandpaper) of the strengthened microcrystalline glass of the present invention can reach more than 2m. At the same time, when dropped from a fixed height of 2.5m, the pass rate of the strengthened microcrystalline glass of the present invention is more than 70%.

[0310] In addition, the high temperature and high humidity failure time of the strengthened microcrystalline glass of the present invention can reach more than 360 hours, indicating that the strengthened microcrystalline glass of the present invention has excellent weather resistance.

[0311] Comparative Examples 1-6 were operated and tested under the same operating conditions as Example 1. Table 6 shows the glass formula compositions of the substrate glasses prepared in Comparative Examples 1-6 and the melting states of the prepared substrate glasses.

[0312] Table 6 Glass formula composition of the prepared substrate glass of Comparative Examples 1-6 and the melting state of the prepared substrate glass

[0313]

[0314] It can be seen from Table 6 that the B value in Comparative Example 1 is 0.89, which is greater than 0.8. Fig. 9 As shown, the substrate glass is ceramicized after melting; Al 2 O 3 Too high content, B2 O 3 The content is low and the A value is 0.24, which is greater than 0.18, resulting in melting defects such as Fig.10 As shown, a large amount of unmelted material appeared in the substrate glass after melting; 2 O 3 The content is small and the A value is 0.21, which is greater than 0.18. Fig.11 As shown, white precipitate appears on the substrate glass after melting; in Comparative Example 4, the ZrO2 content is too high and the A value is 0.19, which is greater than 0.18, and white precipitate appears on the substrate glass after melting; in Comparative Example 5, the MgO content is relatively high and the B value is 0.84, which is greater than 0.8, and the substrate glass is ceramicized after melting; in Comparative Example 6, the ZnO content is relatively high and the B value is 1.05, which is greater than 0.8, and the melting condition is as follows Fig.12 As shown, the base glass becomes ceramic after melting.

[0315] Comparative Examples 7-13 were operated under the same operating conditions as Example 1, and corresponding tests were performed. Table 7 shows the glass formula composition, melting state, heat treatment process and performance parameters of the chemically strengthened microcrystalline glass prepared by Comparative Examples 7-13; Table 8 shows the chemical strengthening conditions of the chemically strengthened microcrystalline glass prepared by Comparative Examples 7-12 and the performance parameters of the strengthened microcrystalline glass prepared by Comparative Examples 7-12. Among them, the glass formula of Comparative Examples 9 and Comparative Examples 13 is the same, that is, the prepared substrate glass is the same. Comparative Example 9 did not undergo nucleation treatment, but only one step of heat treatment, that is, direct temperature increase for crystallization treatment; Comparative Example 13 was crystallized at 800°C for 240 minutes, but no crystals were precipitated, but phase separation occurred, and the transmittance decreased; Comparative Example 12 did not undergo nucleation treatment, and Comparative Example 9 did not undergo ion strengthening treatment; Comparative Example 7 used 450°C×100%NaNO 3 ×9h and 450℃×30%NaNO 3 +70% KNO 3 ×8h two conditions were strengthened.

[0316] Table 7 Glass formula composition, melting state, heat treatment process and performance parameters of chemically strengthened microcrystalline glass prepared by comparative examples 7-13

[0317]

[0318]

[0319]

[0320] Table 8 Chemical strengthening conditions of chemically strengthened glass-ceramics prepared in Comparative Examples 7-12 and performance parameters of the strengthened glass-ceramics prepared therefrom

[0321]

[0322]

[0323] It should be noted that the glass formula of Comparative Example 8 contains K 2 O, therefore, the measured surface K 2 O is not entirely the result of ion exchange, therefore, the surface K of Comparative Example 8 is not given in Table 8. 2 O value.

[0324] Comparative Examples 14-19 were operated under the same operating conditions as Example 1 and were tested accordingly. Table 9 shows the glass formula composition, melting state, heat treatment process and performance parameters of the chemically strengthened glass-ceramics prepared in Comparative Examples 14-19; Table 10 shows the chemical strengthening conditions of the chemically strengthened glass-ceramics prepared in Comparative Examples 14-16 and the performance parameters of the strengthened glass-ceramics prepared therefrom; in addition, Comparative Examples 17-19 were not subjected to strengthening treatment.

[0325] Table 9 Glass formula composition, melting state, heat treatment process and performance parameters of chemically strengthened microcrystalline glass prepared in Comparative Examples 14-19

[0326]

[0327]

[0328]

[0329] Table 10 Chemical strengthening conditions of chemically strengthened glass-ceramics prepared in Comparative Examples 14-16 and performance parameters of the strengthened glass-ceramics prepared therefrom

[0330]

[0331] Note: Since the maximum time for the high temperature and high humidity failure test in the present invention is 360 hours (15 days), if the glass sample is taken out for observation after 360 hours, and the sample still has no spots and / or fog points that cannot be wiped off, it is judged that the high temperature and high humidity failure time of the glass sample is greater than 360 hours.

[0332] It can be seen from Table 7 and Table 9 that the Na 2The O content is low. When the heat treatment temperature is lower than 800°C, no crystalline phase appears in the glass after heat treatment. When the heat treatment temperature reaches 900°C, mullite impurities appear after crystallization. The transmittance of the finally prepared microcrystalline glass sample is low, showing devitrification. The MgO content in Comparative Example 17 is low, the average grain size of the microcrystalline glass sample after crystallization is too large, the transmittance is low, and the optical properties of the sample are poor. The ZnO content in Comparative Example 18 is low, the average grain size of the microcrystalline glass sample after crystallization is too large and impurities appear, the transmittance is low, and the optical properties of the sample are poor. The Li content in Comparative Example 19 is low. 2 The O content is high, the crystallized glass-ceramic sample is seriously foggy, the average grain size is too large and there is impure quartz SS, the transmittance is low, and the optical properties of the sample are extremely poor. Fig.13 shown.

[0333] It can be seen from Tables 8 and 10 that Al 2 O 3 The content is low, and the stress level of the finally prepared strengthened microcrystalline glass is low, and the drop impact resistance is poor; in Comparative Example 12, the X value is 23.94%, the Y value is 44.77%, and in Comparative Example 14, the X value is 29.95%, and the Y value is 55.08%, all of which do not meet the conditions of X=30-50% and Y=60-80%. Finally, the stress level of the strengthened microcrystalline glass prepared by the two is also poor. Specifically, when the drop test is carried out using 120-mesh sandpaper, the average anti-sandpaper drop height of the strengthened microcrystalline glass in Comparative Examples 12 and Comparative Example 14 is less than 1.4m, which is much lower than the strengthened microcrystalline glass prepared in the embodiment of the present invention. At the same time, when the strengthened microcrystalline glass in Comparative Examples 12 and Comparative Example 14 is subjected to a 2.5m fixed-point height drop test, the glass is broken, and the pass rate is 0; the Y value in Comparative Example 15 does not meet the conditions of 60-80%, and the components contain BaO, Al 2 O 3The content of does not meet the requirements of the present invention either. Finally, the stress level of the strengthened microcrystalline glass obtained in Comparative Example 15 is poor. When the drop test is performed using 120-mesh sandpaper, the average sandpaper drop height is 0.6m, which is much lower than the strengthened microcrystalline glass obtained in the embodiment of the present invention. At the same time, when the drop test is performed from a fixed height of 2.5m, the test pass rate of the strengthened microcrystalline glass in Comparative Example 15 is also 0. The X value of Comparative Example 11 is 38.15% and the Y value is 66.64%, but the component contains 2.21mol% of BaO. The stress level obtained after strengthening is low, and the drop impact resistance is poor. The X value of Comparative Example 16 is 35.50% and the Y value is 59.10%. The X value meets the condition of 30-50%, and the Y value does not meet the condition of 60-80%. The deep stress level of the obtained strengthened microcrystalline glass is poor. When the drop test is carried out using 120-mesh sandpaper, the average sandpaper resistance drop height is 1.02m, which is much lower than the strengthened microcrystalline glass obtained in the embodiment of the present invention.

[0334] In summary, the strengthened glass-ceramics made from the chemically strengthened glass-ceramics of the present invention has excellent mechanical properties, such as excellent drop impact resistance. Specifically, the average sandpaper drop resistance height of the strengthened glass-ceramics of the present invention (tested with 120-mesh sandpaper) is as high as 2m or more. At the same time, when performing a fixed-point height drop test of 2.5m, the pass rate of the strengthened glass-ceramics of the present invention is greater than or equal to 70%. The drop level is comparable to that of the high-crystallinity lithium aluminum silicon glass-ceramics strengthened glass in Comparative Example 7, and is much higher than the existing ordinary double-strength glass in Comparative Example 8.

[0335] At the same time, since the present invention does not contain Li 2 O, the raw material cost is much lower than that of comparative example 7 and comparative example 8, and its practical value is very considerable. Moreover, the substrate glass prepared by the glass formula of the present invention can obtain transparent microcrystalline glass with the main crystal phase of zinc-magnesium spinel solid solution, excellent optical properties and high intrinsic strength when the heat treatment temperature does not exceed 800°C. The difficulty of mass production of transparent spinel microcrystalline glass is greatly reduced, and the possibility of mass production is higher, which meets the development needs of energy conservation and carbon reduction in the industry.

[0336] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.

Claims

1. A strengthened glass-ceramic, comprising a compressive stress layer and a tensile stress layer, characterized in that: The strengthened glass-ceramics includes spinel crystals, and the spinel crystals are the main crystal phase of the strengthened glass-ceramics; The composition of the strengthened glass-ceramics substantially does not contain Li2O, and the Li2O content is less than 0.01% by mol%. The strengthened microcrystalline glass satisfies: CS_50≥100MPa, |CT_AV|≥70MPa, DOL_0≥0.13t, t is the thickness of the strengthened microcrystalline glass, the unit is μm, the unit of DOL_0 is μm, and the units of CS_50 and |CT_AV| are MPa; wherein CS_50 is the compressive stress value at a depth of 50μm from the glass surface; |CT_AV| refers to the absolute value of the average tensile stress in the tensile stress layer; and DOL_0 refers to the depth of the compressive stress layer. Calculated in mol% of oxides, the composition of the strengthened microcrystalline glass tensile stress layer includes: SiO2 38.00-48.00%, Al2O3 25.50-30.00%, ZrO2 3.00-5.00%, MgO 5.00-8.00%, ZnO 8.00-14.00%, Na2O 7.20-14.00%, B2O3 3.00-8.00%, K2O 0-2.00% and Y2O 30-1.00%.

2. The tempered glass-ceramics according to claim 1, characterized in that: 500MPa≥CS_50≥140MPa; and / or, 200MPa≥|CT_AV|≥70MPa; And / or, 0.22t≥DOL_0≥0.15t.

3. The tempered glass-ceramics according to claim 1, characterized in that: The |CT_CV| of the strengthened glass-ceramics is ≥80MPa, where the unit of |CT_CV| is MPa, wherein |CT_CV| refers to the absolute value of the maximum value of tensile stress.

4. The tempered glass-ceramics according to claim 2, characterized in that: The |CT_CV| of the strengthened glass-ceramics is ≥80MPa, where the unit of |CT_CV| is MPa, wherein |CT_CV| refers to the absolute value of the maximum value of tensile stress.

5. The tempered glass-ceramics according to claim 1, characterized in that: In the strengthened glass-ceramics, 300MPa≥|CT_CV|≥80MPa, the unit of |CT_CV| is MPa, wherein |CT_CV| refers to the absolute value of the maximum value of tensile stress.

6. The tempered glass-ceramics according to claim 1, characterized in that: The surface K2O concentration of the strengthened microcrystalline glass is ≥9.00wt%.

7. The tempered glass-ceramics according to claim 2, characterized in that: The surface K2O concentration of the strengthened microcrystalline glass is ≥9.00wt%.

8. The tempered glass-ceramics according to claim 3, characterized in that: The surface K2O concentration of the strengthened microcrystalline glass is ≥9.00wt%.

9. The tempered glass-ceramics according to claim 1, characterized in that: The surface K2O of the strengthened microcrystalline glass is 9.00-16.00wt%.

10. The tempered glass-ceramics according to claim 1, characterized in that: The CT_LD of the strengthened microcrystalline glass is 40000MPa / mm-85000MPa / mm.

11. The tempered glass-ceramics according to claim 2, characterized in that: The CT_LD of the strengthened microcrystalline glass is 40000MPa / mm-85000MPa / mm.

12. The tempered glass-ceramics according to claim 3, characterized in that: The CT_LD of the strengthened microcrystalline glass is 40000MPa / mm-85000MPa / mm.

13. The tempered glass-ceramics according to claim 6, characterized in that: The CT_LD of the strengthened microcrystalline glass is 40000MPa / mm-85000MPa / mm.

14. The tempered glass-ceramics according to claim 1, characterized in that: The CT_LD of the strengthened microcrystalline glass is 45000MPa / mm-85000MPa / mm.

15. The tempered glass-ceramics according to claim 1, characterized in that: The CT_LD of the strengthened microcrystalline glass is 48000MPa / mm-85000MPa / mm.

16. The tempered glass-ceramics according to claim 1, characterized in that: The crystallinity of the strengthened microcrystalline glass is ≥20.00wt%.

17. The tempered glass-ceramics according to claim 2, characterized in that: The crystallinity of the strengthened microcrystalline glass is ≥20.00wt%.

18. The tempered glass-ceramics according to claim 3, characterized in that: The crystallinity of the strengthened microcrystalline glass is ≥20.00wt%.

19. The tempered glass-ceramics according to claim 6, characterized in that: The crystallinity of the strengthened microcrystalline glass is ≥20.00wt%.

20. The strengthened glass-ceramics according to claim 10, characterized in that: The crystallinity of the strengthened microcrystalline glass is ≥20.00wt%.

21. The tempered glass-ceramics according to claim 1, characterized in that: The crystallinity of the strengthened microcrystalline glass is 20.00 to 50.00 wt %.

22. The strengthened glass-ceramics according to claim 1, characterized in that: The crystallinity of the strengthened microcrystalline glass is 30.00 to 50.00 wt %.

23. The strengthened glass-ceramics according to claim 1, characterized in that: The crystallinity of the strengthened microcrystalline glass is 35.00-45.00 wt %.

24. The strengthened glass-ceramics according to claim 1, characterized in that: In the strengthened glass-ceramics, the average grain size is ≤15.0nm; And / or, the spinel crystal is (Zn, Mg)Al2O4; and / or, the strengthened glass-ceramics also includes a secondary crystalline phase of tetragonal zirconia.

25. The strengthened glass-ceramics according to claim 2, characterized in that: In the strengthened glass-ceramics, the average grain size is ≤15.0nm; And / or, the spinel crystal is (Zn, Mg)Al2O4; and / or, the strengthened glass-ceramics also includes a secondary crystalline phase of tetragonal zirconia.

26. The tempered glass-ceramics according to claim 3, characterized in that: In the strengthened glass-ceramics, the average grain size is ≤15.0nm; And / or, the spinel crystal is (Zn, Mg)Al2O4; and / or, the strengthened glass-ceramics also includes a secondary crystalline phase of tetragonal zirconia.

27. The tempered glass-ceramics according to claim 6, characterized in that: In the strengthened glass-ceramics, the average grain size is ≤15.0nm; And / or, the spinel crystal is (Zn, Mg)Al2O4; and / or, the strengthened glass-ceramics also includes a secondary crystalline phase of tetragonal zirconia.

28. The strengthened glass-ceramics according to claim 10, characterized in that: In the strengthened glass-ceramics, the average grain size is ≤15.0nm; And / or, the spinel crystal is (Zn, Mg)Al2O4; and / or, the strengthened glass-ceramics also includes a secondary crystalline phase of tetragonal zirconia.

29. The strengthened glass-ceramics according to claim 16, characterized in that: In the strengthened glass-ceramics, the average grain size is ≤15.0nm; And / or, the spinel crystal is (Zn, Mg)Al2O4; and / or, the strengthened glass-ceramics also includes a secondary crystalline phase of tetragonal zirconia.

30. The strengthened glass-ceramics according to claim 24, characterized in that: In the strengthened glass-ceramics, an average grain size is 1.0 to 15.0 nm.

31. The strengthened glass-ceramics according to claim 24, characterized in that: In the strengthened microcrystalline glass, the average grain size is 1 to 10 nm.

32. The strengthened glass-ceramics according to claim 24, characterized in that: In the strengthened microcrystalline glass, the average grain size is 4.5 to 8.0 nm.

33. The strengthened glass-ceramics according to claim 1, characterized in that: The strengthened glass-ceramics is transparent in the visible light range.

34. The strengthened glass-ceramics according to claim 2, characterized in that: The strengthened glass-ceramics is transparent in the visible light range.

35. The strengthened glass-ceramics according to claim 3, characterized in that: The strengthened glass-ceramics is transparent in the visible light range.

36. The strengthened glass-ceramics according to claim 6, characterized in that: The strengthened glass-ceramics is transparent in the visible light range.

37. The strengthened glass-ceramics according to claim 10, characterized in that: The strengthened glass-ceramics is transparent in the visible light range.

38. The strengthened glass-ceramics according to claim 16, characterized in that: The strengthened glass-ceramics is transparent in the visible light range.

39. The strengthened glass-ceramics according to claim 24, characterized in that: The strengthened glass-ceramics is transparent in the visible light range.

40. The strengthened glass-ceramics according to claim 1, characterized in that: The Vickers hardness of the reinforced microcrystalline glass is 700-900 kgf / mm 2 .

41. The strengthened glass-ceramics according to claim 2, characterized in that: The Vickers hardness of the reinforced microcrystalline glass is 700-900 kgf / mm 2 .

42. The strengthened glass-ceramics according to claim 3, characterized in that: The Vickers hardness of the reinforced microcrystalline glass is 700-900 kgf / mm 2 .

43. The strengthened glass-ceramics according to claim 6, characterized in that: The Vickers hardness of the reinforced microcrystalline glass is 700-900 kgf / mm 2 .

44. The strengthened glass-ceramics according to claim 10, characterized in that: The Vickers hardness of the reinforced microcrystalline glass is 700-900 kgf / mm 2 .

45. The strengthened glass-ceramics according to claim 16, characterized in that: The Vickers hardness of the reinforced microcrystalline glass is 700-900 kgf / mm 2 .

46. ​​The strengthened glass-ceramics according to claim 24, characterized in that: The Vickers hardness of the reinforced microcrystalline glass is 700-900 kgf / mm 2 .

47. The strengthened glass-ceramics according to claim 33, characterized in that: The Vickers hardness of the reinforced microcrystalline glass is 700-900 kgf / mm 2 .

48. The strengthened glass-ceramics according to claim 1, characterized in that: The fracture toughness of the strengthened microcrystalline glass is greater than or equal to 1.00 MPa·m 1 / 2 .

49. The strengthened glass-ceramics according to claim 2, characterized in that: The fracture toughness of the strengthened microcrystalline glass is greater than or equal to 1.00 MPa·m 1 / 2 .

50. The strengthened glass-ceramics according to claim 3, characterized in that: The fracture toughness of the strengthened microcrystalline glass is greater than or equal to 1.00 MPa·m 1 / 2 .

51. The strengthened glass-ceramics according to claim 6, characterized in that: The fracture toughness of the strengthened microcrystalline glass is greater than or equal to 1.00 MPa·m 1 / 2 .

52. The strengthened glass-ceramics according to claim 10, characterized in that: The fracture toughness of the strengthened microcrystalline glass is greater than or equal to 1.00 MPa·m 1 / 2 .

53. The strengthened glass-ceramics according to claim 16, characterized in that: The fracture toughness of the strengthened microcrystalline glass is greater than or equal to 1.00 MPa·m 1 / 2 .

54. The strengthened glass-ceramics according to claim 24, characterized in that: The fracture toughness of the strengthened microcrystalline glass is greater than or equal to 1.00 MPa·m 1 / 2 .

55. The strengthened glass-ceramics according to claim 33, characterized in that: The fracture toughness of the strengthened microcrystalline glass is greater than or equal to 1.00 MPa·m 1 / 2 .

56. The strengthened glass-ceramics according to claim 40, characterized in that: The fracture toughness of the strengthened microcrystalline glass is greater than or equal to 1.00 MPa·m 1 / 2 .

57. The strengthened glass-ceramics according to claim 1, characterized in that: The fracture toughness of the strengthened microcrystalline glass is greater than or equal to 1.20 MPa·m 1 / 2 .

58. The strengthened glass-ceramics according to claim 1, characterized in that: The fracture toughness of the strengthened microcrystalline glass is greater than or equal to 1.50 MPa·m 1 / 2 .

59. The strengthened glass-ceramic according to any one of claims 1 to 58, characterized in that: At a thickness of 0.7 mm, the strengthened microcrystalline glass is subjected to a sandpaper drop resistance test using 120-grit sandpaper, and the average sandpaper drop resistance height of the strengthened microcrystalline glass is greater than 1.5 m; the average sandpaper drop resistance height is based on tests of at least 10 samples.

60. The strengthened glass-ceramics according to claim 59, characterized in that: The average sandpaper drop resistance height of the strengthened microcrystalline glass is greater than or equal to 1.80 m.

61. The strengthened glass-ceramics according to claim 59, characterized in that: The average sandpaper drop resistance height of the strengthened microcrystalline glass is 1.80 to 2.50 m.

62. The strengthened glass-ceramics according to claim 59, characterized in that: The average sandpaper drop resistance height of the strengthened microcrystalline glass is 2.00 to 2.50 m.

63. The strengthened glass-ceramics according to any one of claims 1 to 58, characterized in that: At a thickness of 0.7 mm, the tempered glass-ceramics is subjected to a 2.5 m drop test using 120-grit sandpaper. If the glass sample does not break after falling, it is considered to have passed. The pass rate of the tempered glass-ceramics is ≥50%; the pass rate is based on the testing of at least 10 samples.

64. The strengthened glass-ceramics according to claim 59, characterized in that: At a thickness of 0.7 mm, the tempered glass-ceramics is subjected to a 2.5 m drop test using 120-grit sandpaper. If the glass sample does not break after falling, it is considered to have passed. The pass rate of the tempered glass-ceramics is ≥50%; the pass rate is based on the testing of at least 10 samples.

65. The strengthened glass-ceramics according to claim 63, characterized in that: The passing rate of the strengthened microcrystalline glass is ≥60%.

66. The strengthened glass-ceramics according to claim 63, characterized in that: The passing rate of the strengthened microcrystalline glass is ≥70%.

67. The strengthened glass-ceramic according to any one of claims 1 to 58, characterized in that: In the tensile stress layer of the strengthened glass-ceramics: The glass composition of the tensile stress layer of the strengthened glass-ceramics satisfies the following conditions, expressed in terms of the content expressed in molar percentage of oxides: The value of A is calculated based on the following formula (1), and the value of A is less than or equal to 0.

18. (1)A=0.65×Al2O3+3.5×ZrO2-0.8×Na2O-2.5×B2O3; and / or, The value of B is calculated based on the following formula (2), and the value of B is less than or equal to 0.

80. (2)B=3.8×Na2O+B2O3+4.5×MgO+6.0×ZnO-0.4×Al2O3-SiO2.

68. The strengthened glass-ceramics according to claim 59, characterized in that: In the tensile stress layer of the strengthened glass-ceramics: The glass composition of the tensile stress layer of the strengthened glass-ceramics satisfies the following conditions, expressed in terms of the content expressed in molar percentage of oxides: The value of A is calculated based on the following formula (1), and the value of A is less than or equal to 0.

18. (1)A=0.65×Al2O3+3.5×ZrO2-0.8×Na2O-2.5×B2O3; and / or, The value of B is calculated based on the following formula (2), and the value of B is less than or equal to 0.

80. (2)B=3.8×Na2O+B2O3+4.5×MgO+6.0×ZnO-0.4×Al2O3-SiO2.

69. The strengthened glass-ceramics according to claim 63, characterized in that: In the tensile stress layer of the strengthened glass-ceramics: The glass composition of the tensile stress layer of the strengthened glass-ceramics satisfies the following conditions, expressed in terms of the content expressed in molar percentage of oxides: The value of A is calculated based on the following formula (1), and the value of A is less than or equal to 0.

18. (1)A=0.65×Al2O3+3.5×ZrO2-0.8×Na2O-2.5×B2O3; and / or, The value of B is calculated based on the following formula (2), and the value of B is less than or equal to 0.

80. (2)B=3.8×Na2O+B2O3+4.5×MgO+6.0×ZnO-0.4×Al2O3-SiO2.

70. The strengthened glass-ceramics according to claim 67, characterized in that: The value of A is calculated based on formula (1), and the value of A is 0.05 to 0.

15. and / or, The value of B was calculated based on the formula (2) and was found to be 0.60 to 0.

78.

71. The strengthened glass-ceramics according to any one of claims 1 to 58, characterized in that: In the tensile stress layer of the strengthened microcrystalline glass, the molar percentage of SiO2 is 38.00-44.00%; And / or, the molar percentage of Na2O is 7.20-13.00%; And / or, the molar percentage of Al2O3 is 25.50-28.00%; And / or, the molar percentage of MgO is 5.00-7.00%; And / or, the molar percentage of ZnO is 8.00-12.00%; And / or, the molar percentage of B2O3 is 3.00-7.00%.

72. The strengthened glass-ceramics according to claim 59, characterized in that: In the tensile stress layer of the strengthened microcrystalline glass, the molar percentage of SiO2 is 38.00-44.00%; And / or, the molar percentage of Na2O is 7.20-13.00%; And / or, the molar percentage of Al2O3 is 25.50-28.00%; And / or, the molar percentage of MgO is 5.00-7.00%; And / or, the molar percentage of ZnO is 8.00-12.00%; And / or, the molar percentage of B2O3 is 3.00-7.00%.

73. The strengthened glass-ceramics according to claim 63, characterized in that: In the tensile stress layer of the strengthened microcrystalline glass, the molar percentage of SiO2 is 38.00-44.00%; And / or, the molar percentage of Na2O is 7.20-13.00%; And / or, the molar percentage of Al2O3 is 25.50-28.00%; And / or, the molar percentage of MgO is 5.00-7.00%; And / or, the molar percentage of ZnO is 8.00-12.00%; And / or, the molar percentage of B2O3 is 3.00-7.00%.

74. The strengthened glass-ceramics according to claim 67, characterized in that: In the tensile stress layer of the strengthened microcrystalline glass, the molar percentage of SiO2 is 38.00-44.00%; And / or, the molar percentage of Na2O is 7.20-13.00%; And / or, the molar percentage of Al2O3 is 25.50-28.00%; And / or, the molar percentage of MgO is 5.00-7.00%; And / or, the molar percentage of ZnO is 8.00-12.00%; And / or, the molar percentage of B2O3 is 3.00-7.00%.

75. The strengthened glass-ceramics according to claim 71, characterized in that: In the tensile stress layer of the strengthened glass-ceramics, the molar percentage of Na2O is 7.20-12.00%; And / or, the molar percentage of MgO is 5.00-6.50%; And / or, the molar percentage of ZnO is 8.00-10.50%; And / or, the molar percentage of B2O3 is 3.00-6.50%.

76. The strengthened glass-ceramics according to any one of claims 1 to 58, characterized in that: In the tensile stress layer of the strengthened microcrystalline glass, the molar percentages of the components Al2O3, MgO and ZnO satisfy the following relationship: Al2O3-MgO-ZnO=8.00-15.00%.

77. The strengthened glass-ceramics according to claim 59, characterized in that: In the tensile stress layer of the strengthened microcrystalline glass, the molar percentages of the components Al2O3, MgO and ZnO satisfy the following relationship: Al2O3-MgO-ZnO=8.00-15.00%.

78. The strengthened glass-ceramics according to claim 63, characterized in that: In the tensile stress layer of the strengthened microcrystalline glass, the molar percentages of the components Al2O3, MgO and ZnO satisfy the following relationship: Al2O3-MgO-ZnO=8.00-15.00%.

79. The strengthened glass-ceramics according to claim 67, characterized in that: In the tensile stress layer of the strengthened microcrystalline glass, the molar percentages of the components Al2O3, MgO and ZnO satisfy the following relationship: Al2O3-MgO-ZnO=8.00-15.00%.

80. The strengthened glass-ceramics according to claim 71, characterized in that: In the tensile stress layer of the strengthened microcrystalline glass, the molar percentages of the components Al2O3, MgO and ZnO satisfy the following relationship: Al2O3-MgO-ZnO=8.00-15.00%.

81. The strengthened glass-ceramic according to any one of claims 1 to 58, characterized in that: In the tensile stress layer of the strengthened glass-ceramics: The glass composition of the tensile stress layer of the strengthened glass-ceramics satisfies the following conditions, expressed in terms of the content expressed in molar percentage of oxides: The value of X is calculated based on the following formula (3), and the value of X is 30.00 to 50.00%. (3)X=2.1×(Al2O3-MgO-ZnO) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3); and / or, The value of Y is calculated based on the following formula (4), and the value of Y is 60.00 to 80.00%. (4) Y=(2.7×Na2O+1.8×(Al2O3-MgO-ZnO)) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3).

82. The strengthened glass-ceramics according to claim 59, characterized in that: In the tensile stress layer of the strengthened glass-ceramics: The glass composition of the tensile stress layer of the strengthened glass-ceramics satisfies the following conditions, expressed in terms of the content expressed in molar percentage of oxides: The value of X is calculated based on the following formula (3), and the value of X is 30.00 to 50.00%. (3)X=2.1×(Al2O3-MgO-ZnO) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3); and / or, The value of Y is calculated based on the following formula (4), and the value of Y is 60.00 to 80.00%. (4) Y=(2.7×Na2O+1.8×(Al2O3-MgO-ZnO)) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3).

83. The strengthened glass-ceramics according to claim 63, characterized in that: In the tensile stress layer of the strengthened glass-ceramics: The glass composition of the tensile stress layer of the strengthened glass-ceramics satisfies the following conditions, expressed in terms of the content expressed in molar percentage of oxides: The value of X is calculated based on the following formula (3), and the value of X is 30.00 to 50.00%. (3)X=2.1×(Al2O3-MgO-ZnO) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3); and / or, The value of Y is calculated based on the following formula (4), and the value of Y is 60.00 to 80.00%. (4) Y=(2.7×Na2O+1.8×(Al2O3-MgO-ZnO)) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3).

84. The strengthened glass-ceramics according to claim 67, characterized in that: In the tensile stress layer of the strengthened glass-ceramics: The glass composition of the tensile stress layer of the strengthened glass-ceramics satisfies the following conditions, expressed in terms of the content expressed in molar percentage of oxides: The value of X is calculated based on the following formula (3), and the value of X is 30.00 to 50.00%. (3)X=2.1×(Al2O3-MgO-ZnO) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3); and / or, The value of Y is calculated based on the following formula (4), and the value of Y is 60.00 to 80.00%. (4) Y=(2.7×Na2O+1.8×(Al2O3-MgO-ZnO)) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3).

85. The strengthened glass-ceramics according to claim 71, characterized in that: In the tensile stress layer of the strengthened glass-ceramics: The glass composition of the tensile stress layer of the strengthened glass-ceramics satisfies the following conditions, expressed in terms of the content expressed in molar percentage of oxides: The value of X is calculated based on the following formula (3), and the value of X is 30.00 to 50.00%. (3)X=2.1×(Al2O3-MgO-ZnO) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3); and / or, The value of Y is calculated based on the following formula (4), and the value of Y is 60.00 to 80.00%. (4) Y=(2.7×Na2O+1.8×(Al2O3-MgO-ZnO)) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3).

86. The strengthened glass-ceramics according to claim 76, characterized in that: In the tensile stress layer of the strengthened glass-ceramics: The glass composition of the tensile stress layer of the strengthened glass-ceramics satisfies the following conditions, expressed in terms of the content expressed in molar percentage of oxides: The value of X is calculated based on the following formula (3), and the value of X is 30.00 to 50.00%. (3)X=2.1×(Al2O3-MgO-ZnO) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3); and / or, The value of Y is calculated based on the following formula (4), and the value of Y is 60.00 to 80.00%. (4) Y=(2.7×Na2O+1.8×(Al2O3-MgO-ZnO)) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3).

87. The strengthened glass-ceramics according to claim 82, characterized in that: The value of X is calculated based on the following formula (3), and the value of X is 34.00 to 46.00%. and / or, The value of Y was calculated based on the following formula (4), and the value of Y was 60.00 to 75.00%.

88. The strengthened glass-ceramics according to any one of claims 1 to 58, characterized in that: The tensile stress layer of the strengthened microcrystalline glass: substantially does not contain BaO, with a BaO content of less than 0.01% in mol%; and / or substantially does not contain TiO2, with a TiO2 content of less than 0.01% in mol%.

89. The strengthened glass-ceramics according to claim 59, characterized in that: The tensile stress layer of the strengthened microcrystalline glass: substantially does not contain BaO, with a BaO content of less than 0.01% in mol%; and / or substantially does not contain TiO2, with a TiO2 content of less than 0.01% in mol%.

90. The strengthened glass-ceramics according to claim 63, characterized in that: The tensile stress layer of the strengthened microcrystalline glass: substantially does not contain BaO, with a BaO content of less than 0.01% in mol%; and / or substantially does not contain TiO2, with a TiO2 content of less than 0.01% in mol%.

91. The strengthened glass-ceramics according to claim 67, characterized in that: The tensile stress layer of the strengthened microcrystalline glass: substantially does not contain BaO, with a BaO content of less than 0.01% in mol%; and / or substantially does not contain TiO2, with a TiO2 content of less than 0.01% in mol%.

92. The strengthened glass-ceramics according to claim 71, characterized in that: The tensile stress layer of the strengthened microcrystalline glass: substantially does not contain BaO, with a BaO content of less than 0.01% in mol%; and / or substantially does not contain TiO2, with a TiO2 content of less than 0.01% in mol%.

93. The strengthened glass-ceramics according to claim 76, characterized in that: The tensile stress layer of the strengthened microcrystalline glass: substantially does not contain BaO, with a BaO content of less than 0.01% in mol%; and / or substantially does not contain TiO2, with a TiO2 content of less than 0.01% in mol%.

94. The strengthened glass-ceramics according to claim 82, characterized in that: The tensile stress layer of the strengthened microcrystalline glass: substantially does not contain BaO, with a BaO content of less than 0.01% in mol%; and / or substantially does not contain TiO2, with a TiO2 content of less than 0.01% in mol%.

95. The strengthened glass-ceramic according to any one of claims 1 to 58, characterized in that: The Young's modulus of the strengthened microcrystalline glass is ≥100 GPa.

96. The strengthened glass-ceramics according to claim 59, characterized in that: The Young's modulus of the strengthened microcrystalline glass is ≥100 GPa.

97. The strengthened glass-ceramics according to claim 63, characterized in that: The Young's modulus of the strengthened microcrystalline glass is ≥100 GPa.

98. The strengthened glass-ceramics according to claim 67, characterized in that: The Young's modulus of the strengthened microcrystalline glass is ≥100 GPa.

99. The strengthened glass-ceramics according to claim 71, characterized in that: The Young's modulus of the strengthened microcrystalline glass is ≥100 GPa.

100. The strengthened glass-ceramics according to claim 76, characterized in that: The Young's modulus of the strengthened microcrystalline glass is ≥100 GPa.

101. The strengthened glass-ceramics according to claim 82, characterized in that: The Young's modulus of the strengthened microcrystalline glass is ≥100 GPa.

102. The strengthened glass-ceramics according to claim 88, characterized in that: The Young's modulus of the strengthened microcrystalline glass is ≥100 GPa.

103. The strengthened glass-ceramics according to any one of claims 1 to 58, characterized in that: The Young's modulus of the strengthened microcrystalline glass is ≥110 GPa.

104. The strengthened glass-ceramic according to any one of claims 1 to 58, characterized in that: The Young's modulus of the strengthened microcrystalline glass is 114 GPa≤Young's modulus≤140 GPa.

105. A method for preparing the strengthened glass-ceramics according to any one of claims 1 to 104, characterized in that: The method comprises the following steps: (I) preparing chemically strengthened glass-ceramics: the chemically strengthened glass-ceramics are prepared by heat treating a substrate glass; (II) preparing strengthened glass-ceramics: chemically strengthening the chemically strengthened glass-ceramics obtained in step (I) to obtain strengthened glass-ceramics as described in any one of claims 1 to 104; The strengthened glass-ceramics includes spinel crystals, and the spinel crystals are the main crystal phase of the strengthened glass-ceramics; The composition of the strengthened glass-ceramics substantially does not contain Li2O, and the Li2O content is less than 0.01% by mol%. The strengthened microcrystalline glass satisfies: CS_50≥100MPa, |CT_AV|≥70MPa, DOL_0≥0.13t, where t is the thickness of the strengthened microcrystalline glass.

106. The preparation method according to claim 105, characterized in that The chemical strengthening treatment includes a single-step strengthening method or a multi-step strengthening method.

107. The preparation method according to claim 105, characterized in that The chemical strengthening treatment salt bath is a molten salt containing a potassium salt.

108. The preparation method according to claim 106, characterized in that: The chemical strengthening treatment salt bath is a molten salt containing a potassium salt.

109. The preparation method according to claim 107, characterized in that In the salt bath for chemical strengthening treatment, the concentration of potassium salt is 60wt% to 100wt%.

110. The preparation method according to claim 107, characterized in that: In the chemical strengthening treatment salt bath, the temperature of the chemical strengthening treatment salt bath is 380°C to 600°C.

111. The preparation method according to claim 109, characterized in that: In the chemical strengthening treatment salt bath, the temperature of the chemical strengthening treatment salt bath is 380°C to 600°C.

112. The preparation method according to claim 107, characterized in that: In the chemical strengthening treatment salt bath, the temperature of the chemical strengthening treatment salt bath is 400°C to 550°C.

113. A chemically strengthened glass-ceramic for preparing the strengthened glass-ceramic according to any one of claims 1 to 104, characterized in that: The chemically strengthened glass-ceramics contains spinel crystals, and the spinel crystals are the main crystal phase of the chemically strengthened glass-ceramics; The chemically strengthened glass-ceramics comprises, in mol%, the following oxides: SiO2 38.00-48.00%, Al2O3 25.50-30.00%, ZrO2 3.00-5.00%, MgO 5.00-8.00%, ZnO 8.00-14.00%, Na2O 7.20-14.00%, B2O3 3.00-8.00%, K2O 0-2.00% and Y2O 30-1.00%; The chemically strengthened glass-ceramics contains substantially no Li2O, and the content of Li2O is less than 0.01% in mol%.

114. The chemically strengthened glass-ceramics according to claim 113, characterized in that The composition of the chemically strengthened glass-ceramics satisfies the following requirements, expressed in terms of the content expressed as a molar percentage of oxides: A=0.65×Al2O3+3.5×ZrO2-0.8×Na2O-2.5×B2O3, where A≤0.18; and / or, B = 3.8 × Na2O + B2O3 + 4.5 × MgO + 6.0 × ZnO - 0.4 × Al2O3 - SiO2, wherein B ≤ 0.80; and / or, X=2.1×(Al2O3-MgO-ZnO) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3), wherein X=30.00-50.00%; and / or, Y = (2.7 × Na2O + 1.8 × (Al2O3-MgO-ZnO)) / (SiO2 + Al2O3-MgO-ZnO + Na2O + K2O + B2O3), wherein Y = 60.00-80.00%; And / or, in the chemically strengthened glass-ceramics, the molar percentages of the components Al2O3, MgO, and ZnO satisfy the following relationship: Al2O3-MgO-ZnO=8.00-15.00%.

115. The chemically strengthened glass-ceramics according to claim 114, characterized in that: The value of A is 0.05 to 0.15; and / or, the value of B is 0.60 to 0.78; and / or, X=34.00-46.00%; And / or, Y=60.00-75.00%.

116. The chemically strengthened glass-ceramics according to any one of claims 113 to 115, characterized in that The spinel crystal is (Zn, Mg)Al2O4; and / or the chemically strengthened glass-ceramics further includes a secondary crystalline phase of tetragonal zirconia; And / or, the crystallinity of the chemically strengthened glass-ceramics is ≥20.00wt%; And / or, in the chemically strengthened glass-ceramics, the average grain size is ≤15.0 nm; And / or, the Young's modulus of the chemically strengthened glass-ceramics is ≥100 GPa.

117. The chemically strengthened glass-ceramics according to claim 116, characterized in that The crystallinity of the chemically strengthened glass-ceramics is 20.00 to 50.00 wt %.

118. The chemically strengthened glass-ceramics according to claim 116, wherein: The crystallinity of the chemically strengthened glass-ceramics is 30.00 to 50.00 wt %.

119. The chemically strengthened glass-ceramics according to claim 116, wherein: The chemically strengthened glass-ceramics has a crystallinity of 35.00 to 45.00 wt %.

120. The chemically strengthened glass-ceramics according to claim 116, wherein: In the chemically strengthened glass-ceramics, an average crystal grain size is 1.0 to 15.0 nm.

121. The chemically strengthened glass-ceramics according to claim 116, wherein: In the chemically strengthened glass-ceramics, an average grain size is 1.0 to 10.0 nm.

122. The chemically strengthened glass-ceramics according to claim 116, wherein: In the chemically strengthened glass-ceramics, an average grain size is 4.5 to 8.0 nm.

123. The chemically strengthened glass-ceramics according to claim 116, characterized in that: The Young's modulus of the chemically strengthened glass-ceramics is ≥100 GPa.

124. The chemically strengthened glass-ceramics according to claim 116, wherein: The Young's modulus of the chemically strengthened glass-ceramics is ≥110 GPa.

125. The chemically strengthened glass-ceramics according to claim 116, wherein: The Young's modulus of the chemically strengthened glass-ceramics is 114 GPa≤Young's modulus≤140 GPa.

126. Application of the strengthened glass-ceramics described in any one of claims 1-104, the strengthened glass-ceramics prepared by the preparation method described in any one of claims 105-112, or the chemically strengthened glass-ceramics described in any one of claims 113-125 in mobile phone displays, tablet computer displays, handheld game consoles, vehicle central control screens, electronic whiteboard glass, smart home touch screens, vehicle windshields, aircraft windshields or aircraft windshields.

127. Use of the strengthened microcrystalline glass described in any one of claims 1-104, the strengthened microcrystalline glass prepared by the preparation method described in any one of claims 105-112, or the chemically strengthened microcrystalline glass described in any one of claims 113-125 in electronic terminals.

128. Use of the strengthened glass-ceramics described in any one of claims 1-104, the strengthened glass-ceramics prepared by the preparation method described in any one of claims 105-112, or the chemically strengthened glass-ceramics described in any one of claims 113-125 in portable digital devices.

129. An electronic terminal, characterized in that: The electronic terminal comprises the strengthened glass-ceramic according to any one of claims 1-104.

130. A display screen, characterized in that: The display screen comprises the strengthened micro-ceramic glass according to any one of claims 1 to 104.

131. The display screen according to claim 130, characterized in that The display screen includes a mobile phone display screen, a tablet computer display screen, a vehicle central control screen or a smart home touch screen.

132. A windshield, characterized in that: The windshield comprises the strengthened micro-ceramic glass according to any one of claims 1 to 104.

133. The windshield according to claim 132, characterized in that: The windshield includes a vehicle windshield, an aircraft windshield or an aircraft windshield.

Citation Information

Patent Citations

  • Crystallized glass substrate

    CN112512987A

Cited By

  • Chemically strengthened microcrystalline glass and preparation thereof

    CN121672942A

  • Chemically strengthened microcrystalline glass and preparation thereof

    CN121672942B

  • Precursor glass for preparing spinel glass ceramics

    CN121698567A

  • Spinel glass ceramic and preparation method thereof

    CN121698570A

  • Spinel microcrystalline glass and preparation method thereof

    CN121698570B